Polyfunctional vinyl aromatic copolymer and method for manufacturing the same

JP2025029030AInactive Publication Date: 2025-03-05NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024208228
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2024-11-29
Publication Date
2025-03-05
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure 2025029030000001
    Figure 2025029030000001
  • Figure 2025029030000002
    Figure 2025029030000002
  • Figure 2025029030000003
    Figure 2025029030000003
Patent Text Reader

Abstract

To provide a polyfunctional vinyl aromatic copolymer having reactivity and solubility that can be used for manufacturing a copolymer rubber, and a copolymer rubber material having processability, strength and homogeneity obtained therefrom.SOLUTION: A polyfunctional vinyl aromatic copolymer includes: 5 mol% or more and 30 mol% or less of a structural unit (a) derived from a divinyl aromatic compound, 5 mol% or more and 20 mol% or less of a structural unit (b) derived from a monovinyl aromatic compound, and 50 mol% or more and 90 mol% or less of a structural unit (c) derived from an acenaphthylene-based compound. At least some of the structural units (a) are vinyl group-containing structural units (a1) represented by the following formula (1) (where, R1 represents an aromatic hydrocarbon group having 6-30 carbon atoms). The molar fraction of the vinyl group-containing structural unit (a1) relative to the total of structural units (a), (b), and (c) is in the range of 0.01-0.30.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] In particular, the present invention relates to a polyfunctional vinyl aromatic copolymer having excellent copolymerization reactivity with a conjugated diene compound (B) and an aromatic vinyl compound (C) in the presence of an anionic polymerization initiator, a method for producing the same, a conjugated diene-based copolymer having excellent processability, tensile strength and abrasion resistance, a conjugated diene-based copolymer composition comprising the conjugated diene-based copolymer, and a cross-linked rubber product and tire member obtained by cross-linking the same. [Background technology]

[0002] Conjugated diene rubbers such as SBR (styrene-butadiene rubber), BR (butadiene rubber), and IR (isoprene rubber) styrene-isoprene rubber have excellent abrasion resistance, elasticity, and water resistance, and are used for a variety of purposes such as molding materials and resin modifiers.

[0003] One of the main applications of this conjugated diene rubber is automobile tires. The characteristics required for tires include mechanical strength, abrasion resistance, wet grip properties, etc. (hereinafter, collectively referred to as strength, etc.). Furthermore, in recent years, there has been active development of tires with excellent energy-saving performance, that is, low fuel consumption (so-called "eco tires"). In addition to strength, these eco tires are required to have low rolling resistance.

[0004] It is known that fillers (reinforcing fillers) such as carbon black and silica are added to conjugated diene rubber to ensure the strength of tires, but terminal-modified solution-polymerized SBR (terminal-modified S-SBR) has attracted attention as a material that further improves the strength of tires and gives them excellent rolling resistance. Terminal-modified S-SBR has functional groups at the molecular ends of SBR, and these functional groups at the molecular ends interact with the filler. This interaction improves the dispersion of the filler in SBR, and also restricts the molecular ends of SBR, reducing mobility. As a result, the hysteresis loss (internal friction) of the tire is reduced, and the rolling resistance is reduced. Taking advantage of this characteristic, eco-tires that combine strength and low rolling resistance are being developed.

[0005] For example, in Patent Document 1, an organolithium compound is used as an initiator in a non-polar solvent to synthesize a block copolymer consisting of an α-methylstyrene block and a butadiene block by living anionic polymerization, and if necessary, a polyfunctional coupling agent is reacted to obtain an S-SBR that combines high-temperature characteristics and rubber-like properties. Patent Document 2 discloses a star-shaped block interpolymer having a random copolymer block of a conjugated diene and a monovinyl aromatic monomer, a polyconjugated diene block, and a functional group derived from a polyfunctional lithium-based initiator, and discloses that the star-shaped block interpolymer can be widely used as a rubber in the manufacture of tire treads having excellent properties such as reduced rolling resistance and improved traction characteristics. Patent Documents 1 and 2 are believed to be effective in ensuring the processability of rubber by introducing a branched structure into the rubber component. However, there is no particular ingenuity in the interaction with the filler to ensure strength, and the contribution to strength is insufficient.

[0006] Patent Document 3 discloses a rubber composition in which a rubber composition containing a blend of multiple diene rubbers and a predetermined amount of carbon black is blended with a low molecular weight functional group-containing polymer having a functional group at the molecular chain end that interacts with carbon black and having a polymer structure similar to that of the rubber component of the diene rubber. This rubber composition can control the amount of carbon black distributed in each diene rubber component by blending a low molecular weight compound that interacts with carbon black into the rubber. Therefore, it is possible to effectively express the characteristics of each rubber component and achieve a balance between rubber characteristics that are in a trade-off relationship, such as rolling properties and wet properties. However, this technology does not contribute enough to strength because a low molecular weight compound is blended into the rubber. Patent Document 4 discloses a rubber composition containing a conjugated diene monomer unit, an aromatic vinyl monomer unit, and a crosslinked rubber particle containing a monomer unit having at least two polymerizable unsaturated groups, and a conjugated diene / aromatic vinyl copolymer rubber containing a conjugated diene monomer unit having a specific bond structure, and discloses that the crosslinked rubber particle may contain a monomer unit having a carboxylic acid group, a hydroxyl group, and / or an epoxy group. This technology has an appropriate interaction with an inorganic filler such as silica, and therefore is excellent in dispersibility and processability of the inorganic filler. However, the substances disclosed as the monomer unit having at least two polymerizable unsaturated groups and the monomer unit having a carboxylic acid group, a hydroxyl group, and / or an epoxy group are all low molecular weight. Therefore, there was a risk that the reactivity was excessively high and gelation would progress in the crosslinked rubber particle and the rubber composition. In addition, this technology requires synthesizing a crosslinked rubber separately from the conjugated diene / aromatic vinyl copolymer rubber and then blending the crosslinked rubber with the conjugated diene / aromatic vinyl copolymer rubber, and improvement is needed from the viewpoint of process simplicity.

[0007] In view of the above problems, the present applicant has discovered that a copolymer rubber having processability, strength, and homogeneity can be provided by using a specific polyfunctional vinyl aromatic copolymer compound, which has both a branched structure and a function of interacting with a filler, as a constituent unit of a conjugated diene rubber (Patent Document 5). Although this polyfunctional vinyl aromatic copolymer compound has a significantly improved gelation resistance, it still has a problem of a small amount of microgel being produced as a by-product.

[0008] The present applicant has disclosed compounds similar to the polyfunctional vinyl aromatic copolymer compound disclosed in Patent Document 5 in Patent Documents 6 and 7, etc. However, there is no teaching that these similar compounds can be used as structural units of copolymer rubber. In addition, the polyfunctional vinyl aromatic copolymer disclosed in Patent Document 8 is a copolymer having a wide molecular weight distribution containing a large amount of high molecular weight components with significantly developed branched structures, and therefore, when used as a structural unit of a copolymer rubber, there is a problem that a small amount of microgel is by-produced. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2003-73434 A [Patent Document 2] Special Publication No. 2004-517202 [Patent Document 3] JP 2005-213381 A [Patent Document 4] International Publication No. 2002 / 000779 [Patent Document 5] International Publication No. 2018 / 084128 [Patent Document 6] JP 2004-123873 A [Patent Document 7] JP 2018-39995 A [Patent Document 8] International Publication No. 2018 / 181842 Summary of the Invention

[0010] The present invention aims to solve the above problems, to obtain a polyfunctional vinyl aromatic copolymer having sufficient reactivity and solubility to be used in the production of copolymer rubber without producing a small amount of by-product microgel, and to provide a copolymer rubber material having excellent processability, strength and homogeneity.

[0011] As a result of intensive research, the present inventors have discovered, as a first invention, that a polyfunctional vinyl aromatic copolymer containing a structural unit (a) derived from a divinyl aromatic compound, a structural unit (b) derived from a monovinyl aromatic compound, and a structural unit (c) derived from a cycloolefin monomer having an aromatic condensed ring structure has high reactivity in the production of a copolymer rubber, and that the above-mentioned problems can be solved by using this polyfunctional vinyl aromatic copolymer as a structural unit of a conjugated diene rubber, thereby completing the present invention.

[0012] The first invention relates to a polyfunctional vinyl aromatic copolymer containing 5 mol % or more and 35 mol % or less of structural units (a) derived from a divinyl aromatic compound, 5 mol % or more and 25 mol % or less of structural units (b) derived from a monovinyl aromatic compound, and 40 mol % or more and 90 mol % or less of structural units (c) derived from a cycloolefin monomer having an aromatic condensed ring structure, wherein at least a part of the structural units (a) is a vinyl group-containing structural unit (a1) represented by the following formula (1): [ka] (In the formula, R1 represents an aromatic hydrocarbon group having 6 to 30 carbon atoms.) The polyfunctional vinyl aromatic copolymer is characterized in that the molar fraction of the vinyl group-containing structural unit (a1) relative to the total of the structural units (a), (b) and (c) is in the range of 0.01 to 0.30.

[0013] The polyfunctional vinyl aromatic copolymer has a number average molecular weight Mn of 300 to 100,000, a molecular weight distribution (Mw / Mn) represented by the ratio of the weight average molecular weight Mw to the number average molecular weight Mn of 10.0 or less, and can be soluble in toluene, xylene, tetrahydrofuran, dichloroethane, or chloroform.

[0014] The cycloolefin monomer may be one or more monomers selected from the group consisting of indene compounds, acenaphthylene compounds, benzofuran compounds, and benzothiophene compounds.

[0015] The present invention also relates to a method for producing the polyfunctional vinyl aromatic copolymer, characterized in that polymerization raw materials including a divinyl aromatic compound, a monovinyl aromatic compound, and a cycloolefin monomer having an aromatic condensed ring structure are dissolved in a solvent having a dielectric constant of 2.0 to 15.0, and polymerized in the presence of a Lewis acid catalyst at a temperature of 20 to 120°C.

[0016] The present invention also relates to a conjugated diene-based copolymer obtained by copolymerizing the above-mentioned polyfunctional vinyl aromatic copolymer (A) with a conjugated diene compound (B), or the conjugated diene compound (B) and an aromatic vinyl compound (C).

[0017] The conjugated diene copolymer preferably contains 0.001 to 6% by weight of structural unit (A1) derived from a polyfunctional vinyl aromatic copolymer, 29 to 99.999% by weight of structural unit (B1) derived from a conjugated diene compound, and 0 to 70% by weight of structural unit (C1) derived from an aromatic vinyl compound. The conjugated diene copolymer may also be obtained by reacting a modifier with the polymerization active terminal of the conjugated diene copolymer.

[0018] The present invention also relates to a conjugated diene copolymer composition, characterized in that it contains 0.5 to 200 parts by weight of at least one reinforcing filler selected from the group consisting of silica-based inorganic fillers, metal oxides, metal hydroxides, and carbon black, based on 100 parts by weight of the above-mentioned conjugated diene copolymer.

[0019] The conjugated diene copolymer composition may further contain a crosslinking agent. The present invention also relates to a cross-linked rubber product obtained by cross-linking the above conjugated diene copolymer composition containing a cross-linking agent.

[0020] The present invention also relates to a tire member comprising the above-mentioned conjugated diene copolymer composition.

[0021] As a result of intensive research, the present inventors have discovered, as a second invention, that a polyfunctional vinyl aromatic copolymer containing a structural unit (a) derived from a divinyl aromatic compound and a structural unit (b) derived from a monovinyl aromatic compound and having a specific crosslinking degree, molar fraction of vinyl group-containing structural units and solubility has high reactivity in the production of a copolymer rubber, and that the above-mentioned problems can be solved by using this polyfunctional vinyl aromatic copolymer as a structural unit of a conjugated diene rubber, thereby completing the present invention.

[0022] The second invention is a polyfunctional vinyl aromatic copolymer containing 0.5 mol % or more and 40 mol % or less of structural units (a) derived from a divinyl aromatic compound and 60 mol % or more and 99.5 mol % or less of structural units (b) derived from a monovinyl aromatic compound, wherein at least a part of the structural units (a) is a crosslinked structural unit (a2) represented by the following formula (2) and a vinyl group-containing structural unit (a1) represented by the following formula (1): [ka] (In the formula, R1 independently represents an aromatic hydrocarbon group having 6 to 30 carbon atoms.) The molar fraction of the crosslinked structural unit (a2) relative to the structural unit (a) is in the range of 0.05 to 0.50, the molar fraction of the vinyl group-containing structural unit (a1) relative to the sum of the structural units (a) and (b) is in the range of 0.001 to 0.35, the number average molecular weight Mn of the polyfunctional vinyl aromatic copolymer is 1,000 to 50,000, and the molecular weight distribution (Mw / Mn), which is expressed as the ratio of the weight average molecular weight Mw to the number average molecular weight Mn, is 8.0 or less.

[0023] A sample obtained by dissolving 0.5 g of the polyfunctional vinyl aromatic copolymer in 100 g of toluene is placed in a quartz cell, and the haze (turbidity) of the sample is measured using an integrating sphere type light transmittance measuring device with toluene as a reference sample. The haze value can be 0.1 or less.

[0024] The monovinyl aromatic compound may be one or more monomers selected from the group consisting of styrene, vinylnaphthalene, vinylbiphenyl, m-methylstyrene, p-methylstyrene, o,p-dimethylstyrene, m-ethylvinylbenzene, and p-ethylvinylbenzene.

[0025] The present invention also relates to a method for producing the polyfunctional vinyl aromatic copolymer, which comprises polymerizing a polymerization raw material containing a divinyl aromatic compound and a monovinyl aromatic compound in a homogeneous solvent having a dielectric constant of 2.0 to 15.0 in the presence of a Lewis acid catalyst at a temperature of 20 to 120°C.

[0026] The present invention also relates to a conjugated diene-based copolymer obtained by copolymerizing the above-mentioned polyfunctional vinyl aromatic copolymer (A) with a conjugated diene compound (B), or the conjugated diene compound (B) and an aromatic vinyl compound (C).

[0027] The conjugated diene copolymer preferably contains 0.001 to 6% by weight of structural unit (A1) derived from a polyfunctional vinyl aromatic copolymer, 29 to 99.999% by weight of structural unit (B1) derived from a conjugated diene compound, and 0 to 70% by weight of structural unit (C1) derived from an aromatic vinyl compound. The conjugated diene copolymer may also be obtained by further reacting a modifier with the polymerization active terminal of the conjugated diene copolymer.

[0028] The present invention also relates to a conjugated diene copolymer composition, characterized in that it contains 0.5 to 200 parts by weight of at least one reinforcing filler selected from the group consisting of silica-based inorganic fillers, metal oxides, metal hydroxides, and carbon black, based on 100 parts by weight of the above-mentioned conjugated diene copolymer.

[0029] The conjugated diene copolymer composition may further contain a crosslinking agent. The present invention also relates to a cross-linked rubber product obtained by cross-linking the above conjugated diene copolymer composition containing a cross-linking agent.

[0030] The present invention also relates to a tire member comprising the above-mentioned conjugated diene copolymer composition.

[0031] As a result of intensive research, the present inventors have discovered, as a third invention, that a polyfunctional vinyl aromatic copolymer divinylaromatic compound containing a structural unit (a) derived from a divinylaromatic compound, a structural unit (b) derived from a monovinyl aromatic compound having no substituent at the α-position, and a structural unit (c) derived from an α,α-disubstituted olefin compound has high reactivity in the production of a copolymer rubber, and that the above-mentioned problems can be solved by using this polyfunctional vinyl aromatic copolymer as a structural unit of a conjugated diene rubber, thereby completing the present invention.

[0032] The third invention is a polyfunctional vinyl aromatic copolymer containing 0.5 mol % or more and 75 mol % or less of structural units (a) derived from a divinyl aromatic compound, 5.0 mol % or more and 75 mol % or less of structural units (b) derived from a monovinyl aromatic compound having no substituent at the α-position, and 5.0 mol % or more and 75 mol % or less of structural units (c) derived from an α,α-disubstituted olefin compound, wherein at least a part of the structural units (a) is a crosslinked structural unit (a2) represented by the following formula (2) and a vinyl group-containing structural unit (a1) represented by the following formula (1): [ka] (In the formula, R1 independently represents an aromatic hydrocarbon group having 6 to 30 carbon atoms.) the molar fraction of the crosslinking structural unit (a2) relative to the structural unit (a) is in the range of 0.05 to 0.60, and the molar fraction of the vinyl group-containing structural unit (a1) relative to the sum of the structural units (a), (b) and (c) is in the range of 0.001 to 60; The polyfunctional vinyl aromatic copolymer has a number average molecular weight Mn of 300 to 50,000 and a molecular weight distribution (Mw / Mn) represented by the ratio of the weight average molecular weight Mw to the number average molecular weight Mn of 10.0 or less.

[0033] The α,α-disubstituted olefin compound may be one or more monomers selected from the group consisting of isobutylene, diisobutylene, 2-methyl-1-butene, 2-methyl-1-pentene, 1-methyl-1-cyclopentene, 2-methyl-1-hexene, 1-methyl-1-cyclohexene, 2-methyl-1-heptene, 2-methyl-1-octene, 2-methyl-1-nonene, 2-methyl-1-decene, 2-methyl-1-dodecene, 2-methyl-1-tetradecene, 2-methyl-1-hexadecene, 2-methyl-1-octadecene, 2-methyl-1-eicosene, 2-methyl-1-docosene, 2-methyl-1-tetracosene, and α-methylstyrene. The monovinyl aromatic compound having no substituent at the α-position may be one or more monomers selected from the group consisting of styrene, vinylnaphthalene, vinylbiphenyl, m-methylstyrene, p-methylstyrene, o,p-dimethylstyrene, m-ethylvinylbenzene, and p-ethylvinylbenzene.

[0034] The present invention also relates to a method for producing the above-mentioned polyfunctional vinyl aromatic copolymer, which comprises polymerizing polymerization raw materials including a divinyl aromatic compound, a monovinyl aromatic compound having no substituent at the α-position, and an α,α-disubstituted olefin compound in a homogeneous solvent having a dielectric constant of 2.0 to 15.0 in the presence of a Lewis acid catalyst at a temperature of 0 to 120°C.

[0035] The present invention also relates to a conjugated diene-based copolymer obtained by copolymerizing the above-mentioned polyfunctional vinyl aromatic copolymer (A) with a conjugated diene compound (B), or the conjugated diene compound (B) and an aromatic vinyl compound (C).

[0036] The conjugated diene copolymer preferably contains 0.001 to 6% by weight of structural unit (A1) derived from a polyfunctional vinyl aromatic copolymer, 29 to 99.999% by weight of structural unit (B1) derived from a conjugated diene compound, and 0 to 70% by weight of structural unit (C1) derived from an aromatic vinyl compound. The conjugated diene copolymer may also be obtained by further reacting a modifier with the polymerization active terminal of the conjugated diene copolymer. The composition may contain 0.5 to 200 parts by weight of at least one reinforcing filler selected from the group consisting of silica-based inorganic fillers, metal oxides, metal hydroxides, and carbon black, based on 100 parts by weight of the conjugated diene copolymer. The conjugated diene copolymer composition may further contain a crosslinking agent.

[0037] The present invention also relates to a cross-linked rubber product obtained by cross-linking the above conjugated diene copolymer composition containing a cross-linking agent. The present invention also relates to a tire member comprising the above-mentioned conjugated diene copolymer composition.

[0038] The polyfunctional vinyl aromatic copolymer of the present invention has reactivity and solubility that can be used to produce copolymer rubber, and is therefore suitable as a raw material. The conjugated diene copolymer of the present invention has a structural unit that has both a branched structure and a function of interacting with a filler, and therefore is excellent as a rubber that combines processability and strength. Furthermore, it is less likely to form gel-like substances and is homogeneous, and can be used as a molding material, a resin modifier, etc. Furthermore, a crosslinked rubber composition obtained by incorporating a filler in this conjugated diene copolymer and crosslinking the same has excellent filler dispersibility and therefore has excellent mechanical strength and abrasion resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0039] The first polyfunctional vinyl aromatic copolymer of the present invention will be described.

[0040] The polyfunctional vinyl aromatic copolymer of the present invention contains a structural unit (a) derived from a divinyl aromatic compound, a structural unit (b) derived from a monovinyl aromatic compound, and a structural unit (c) derived from a cycloolefin monomer containing an aromatic condensed ring structure. It is preferable that the number average molecular weight Mn is 300 to 100,000, the molecular weight distribution (Mw / Mn) represented by the ratio of the weight average molecular weight Mw to the number average molecular weight Mn is 10.0 or less, and the polymer is soluble in toluene, xylene, tetrahydrofuran, dichloroethane, or chloroform.

[0041] The polyfunctional vinyl aromatic copolymer of the present invention is preferably soluble in a solvent, and is therefore also called a soluble polyfunctional vinyl aromatic copolymer, or simply a copolymer. The structural unit referred to in this specification refers to a repeating unit present in the main chain of the copolymer.

[0042] The structural unit (a) derived from a divinyl aromatic compound may have several different structures, such as one in which only one vinyl group has reacted and one in which two vinyl groups have reacted. However, the structural unit contains the vinyl group-containing structural unit (a1) represented by the above formula (1), which is a structural unit in which only one vinyl group has reacted, in a molar fraction in the range of 0.01 to 0.30. The preferred lower limit is 0.04, more preferably 0.05. The preferred upper limit is 0.25, more preferably 0.20. By setting the molar fraction within the above range, it is possible to obtain a copolymer rubber that has excellent reactivity during copolymerization with a conjugated diene compound while maintaining solubility, has excellent compatibility with diene rubber, and is also excellent in processability, tensile strength, and abrasion resistance. If the molar fraction is less than 0.01, the copolymerization reactivity with a conjugated diene compound, etc. tends to decrease, and if it is greater than 0.30, microgels tend to be generated during copolymerization. Here, the above molar fraction is the molar fraction of the vinyl group-containing structural unit (a1) relative to the total of the structural units (a), (b) and (c), and is calculated by the following formula (12). (a1) / [(a)+(b)+(c)] (12) Here, (a), (b), (c) and (a1) indicate the amounts (moles) of the structural units (a), (b), (c) and (a1), respectively.

[0043] The polyfunctional vinyl aromatic copolymer of the present invention preferably contains 5 to 35 mol % of the structural unit (a) derived from a divinyl aromatic compound. When the structural units are composed only of the structural units (a), (b), and (c), the molar fraction of the structural unit (a) is 0.05 to 0.35 relative to the total of the structural units (a), (b), and (c). This molar fraction is calculated by the following formula (13). (a) / [(a)+(b)+(c)] (13) (Here, (a), (b), and (c) are defined as the same as in formula (2).) The lower limit of the molar fraction is preferably 0.06, more preferably 0.07, and the upper limit is preferably 0.30, more preferably 0.25. In the case where structural units other than the structural units (a), (b) and (c) are contained, the lower limit is preferably 0.02, more preferably 0.05, and even more preferably 0.07, and the upper limit is preferably 0.35, more preferably 0.30, and even more preferably 0.25.

[0044] On the other hand, the molar fraction of the structural unit (b) derived from the monovinyl aromatic compound is 0.05 to 0.25. The lower limit is preferably 0.07. The upper limit is preferably 0.23, more preferably 0.20.

[0045] The molar fraction of the structural unit (c) derived from the cycloolefin monomer is 0.40 to 0.90, with the lower limit being preferably 0.45, more preferably 0.50, and even more preferably 0.65, and the upper limit being preferably 0.86, more preferably 0.80. When the polymer consists only of structural units (a), (b), and (c), the molar fraction of the structural unit (b) is calculated by the following formula (14), and the molar fraction of the structural unit (c) is calculated by the following formula (15). (b) / [(a)+(b)+(c)] (14) (c) / [(a)+(b)+(c)] (15) (Here, (a), (b), and (c) are defined as the same as in formula (12).) Even when structural units other than the structural units (a), (b) and (c) are contained, the preferred molar fraction of the structural unit (b) or the structural unit (c) is within the above range.

[0046] The structural unit (a) derived from a divinyl aromatic compound contains a vinyl group as a branching component for expressing copolymerization reactivity with a conjugated diene compound, while the structural unit (b) derived from a monovinyl aromatic compound does not have a vinyl group involved in the curing reaction, and thus provides moldability, compatibility, etc. In addition, the structural unit (c) derived from a cycloolefin monomer provides reactivity, ease of gel formation, and compatibility, since the amount of introduction affects the molecular weight and molecular weight distribution of the polyfunctional vinyl aromatic copolymer. Therefore, if the molar fraction of the structural unit (a) is less than 0.05, the heat resistance of the cured product is insufficient, and if it exceeds 0.35, the moldability is reduced. In addition, if the molar fraction of the structural unit (b) is more than 0.25, the heat resistance is reduced, and if it is less than 0.05, the moldability is reduced. On the other hand, if the molar fraction of the structural unit (c) is more than 0.90, the heat resistance is reduced, and if it is less than 0.40, the moldability is reduced.

[0047] The Mn (number average molecular weight in terms of standard polystyrene measured by gel permeation chromatography) of the polyfunctional vinyl aromatic copolymer of the present invention is preferably 300 to 100,000, more preferably 400 to 50,000, and even more preferably 500 to 10,000. If Mn is less than 300, the amount of monofunctional copolymer contained in the copolymer increases, so that the copolymerization reactivity with the conjugated diene compound tends to decrease, and if Mn exceeds 100,000, gel tends to be easily generated, and moldability and tensile elongation at break tend to decrease. The molecular weight distribution (Mw / Mn) value is preferably 10.0 or less, more preferably 8.0 or less, more preferably 1.0 to 7.0. Most preferably 1.3 to 6.0. If Mw / Mn exceeds 10.0, the processability of the copolymer rubber tends to deteriorate, and gel tends to be generated.

[0048] The soluble polyfunctional vinyl aromatic copolymer of the present invention is soluble in a solvent selected from toluene, xylene, tetrahydrofuran, dichloroethane, or chloroform, and is preferably soluble in any of the above solvents. In order to be a solvent-soluble polyfunctional copolymer, it is necessary that a part of the vinyl group of divinylbenzene remains uncrosslinked and has an appropriate degree of branching. Such a copolymer or its manufacturing method is known in the above patent documents. It is preferable that the copolymer dissolves in an amount of 50 g or more in 100 g of solvent. More preferably, the copolymer dissolves in an amount of 80 g or more.

[0049] The second polyfunctional vinyl aromatic copolymer of the present invention will now be described.

[0050] The polyfunctional vinyl aromatic copolymer of the present invention contains structural units (a) derived from a divinyl aromatic compound and structural units (b) derived from a monovinyl aromatic compound. At least a part of the structural unit (a) contains the crosslinked structural unit (a2) represented by the above formula (2) and the vinyl group-containing structural unit (a1) represented by the above formula (1). The molar fraction (also referred to as the degree of crosslinking) of the crosslinked structural unit (a2) derived from a divinylaromatic compound relative to the structural unit (a) is in the range of 0.05 to 0.50, and the molar fraction of the vinyl group-containing structural unit (a1) relative to the sum of the structural units (a) and (b) is in the range of 0.001 to 0.35.

[0051] The degree of crosslinking of the crosslinking structural unit (a2) is in the range of 0.05 to 0.50, with a preferred lower limit of 0.06, and more preferably 0.07. The preferred upper limit is 0.45, and more preferably 0.40. Particularly preferably 0.35, and most preferably 0.30. By setting the degree of crosslinking within the above range, it is possible to obtain a copolymer rubber that has excellent reactivity during copolymerization with a conjugated diene compound while maintaining solubility, has excellent compatibility with diene rubber, and is also excellent in processability, tensile strength, and abrasion resistance. According to the method for producing a polyfunctional vinyl aromatic copolymer of the present invention, the degree of crosslinking and the vinyl group-containing structural unit (a1) represented by the formula (1) described below are parameters that can be independently controlled and changed arbitrarily. However, if the degree of crosslinking is less than 0.05, the degree of crosslinking of the polyfunctional vinyl aromatic copolymer is small, and therefore a crosslinking reaction is likely to occur within the molecule of the vinyl group-containing structural unit (a1) represented by the formula (1), and microgels tend to be formed during copolymerization with a conjugated diene compound or the like. On the other hand, if it is greater than 0.50, the molecular weight of the polyfunctional vinyl aromatic copolymer itself increases, and the molecular weight distribution tends to broaden, so that the abrasion resistance tends to decrease.

[0052] The structural unit (a) derived from a divinyl aromatic compound may have several different structures, such as one in which only one vinyl group has reacted and one in which two vinyl groups have reacted, but the vinyl-group-containing structural unit (a1) represented by the above formula (1), which is a structural unit having a structure in which only one vinyl group has reacted, is contained in the above molar fraction in the range of 0.001 to 0.35. The preferred lower limit is 0.005, more preferably 0.01. The preferred upper limit is 0.30, more preferably 0.20. By setting the molar fraction within the above range, it is possible to obtain a copolymer rubber that has excellent reactivity during copolymerization with a conjugated diene compound while maintaining solubility, has excellent compatibility with diene rubber, and is also excellent in processability, tensile strength, and abrasion resistance. If the molar fraction is less than 0.001, the copolymerization reactivity with a conjugated diene compound, etc. tends to decrease, and if it is greater than 0.35, microgels tend to be generated during copolymerization. Here, the above molar fraction is the molar fraction of the vinyl group-containing structural unit (a1) relative to the sum of the structural units (a) and (b), and is calculated by the following formula (23). (a1) / [(a)+(b)] (23) Here, (a), (b) and (a1) indicate the amounts (moles) of the structural units (a), (b) and (a1), respectively.

[0053] The polyfunctional vinyl aromatic copolymer of the present invention contains 0.5 to 40 mol % of the structural unit (a) derived from a divinyl aromatic compound. When the structural units consist only of the structural units (a) and (b), the molar fraction of the structural unit (a) is 0.005 to 0.40 relative to the sum of the structural units (a) and (b). This molar fraction is calculated by the following formula (24). (a) / [(a)+(b)] (24) (Here, (a) and (b) are defined as the same as in formula (23).) The lower limit of the molar fraction is preferably 0.006, more preferably 0.007, and the upper limit is preferably 0.30, more preferably 0.25. In the case where structural units other than the structural units (a) and (b) are contained, the lower limit of the content is preferably 0.2 mol%, more preferably 0.5 mol%, and even more preferably 0.7 mol%, and the upper limit is preferably 35 mol%, more preferably 30 mol%, and even more preferably 25 mol%.

[0054] On the other hand, the molar fraction of the structural unit (b) derived from the monovinyl aromatic compound is 0.60 to 0.995. The lower limit is preferably 0.70. The lower limit is more preferably 0.75. The upper limit is preferably 0.994, more preferably 0.993.

[0055] When the polymer consists only of the structural units (a) and (b), the molar fraction of the structural unit (b) is calculated by the following formula (25). (b) / [(a)+(b)] (25) (Here, (a) and (b) are defined as the same as in formula (23).) Even when structural units other than the structural units (a) and (b) are contained, the molar fraction of the structural unit (b) is preferably within the above range.

[0056] The structural unit (a) derived from a divinyl aromatic compound contains a vinyl group as a branching component for expressing copolymerization reactivity with a conjugated diene compound, while the structural unit (b) derived from a monovinyl aromatic compound does not have a vinyl group involved in the curing reaction, and therefore provides moldability, compatibility, etc. Therefore, if the molar fraction of the structural unit (a) is less than 0.005, the heat resistance of the cured product is insufficient, and if it exceeds 0.40, the moldability is reduced. In addition, if the molar fraction of the structural unit (b) is more than 0.995, the heat resistance is reduced, and if it is less than 0.60, the moldability is reduced.

[0057] The polyfunctional vinyl aromatic copolymer of the present invention may contain other structural units in addition to the above structural units, the details of which will be understood from the explanation of the production method.

[0058] The Mn (number average molecular weight in terms of standard polystyrene measured by gel permeation chromatography) of the polyfunctional vinyl aromatic copolymer of the present invention is 1,000 to 50,000, preferably 1,200 to 45,000, more preferably 1,400 to 30,000. It is further preferably 1,600 to 20,000, and most preferably 2,000 to 10,000. If Mn is less than 1,000, the amount of monofunctional copolymer contained in the copolymer increases, so that the copolymerization reactivity with the conjugated diene compound tends to decrease, and if it exceeds 50,000, gel tends to be easily generated, and moldability and tensile elongation at break tend to decrease. The molecular weight distribution is 8.0 or less, preferably 7.0 or less, more preferably 1.3 to 6.0. If Mw / Mn exceeds 8.0, the processability of the copolymer rubber tends to deteriorate, and gel tends to be generated.

[0059] The polyfunctional vinyl aromatic copolymer of the present invention is soluble in a solvent selected from toluene, xylene, tetrahydrofuran, dichloroethane, or chloroform, and is preferably soluble in any of the above solvents. In order to be a solvent-soluble, polyfunctional copolymer, it is necessary that a portion of the vinyl groups of divinylbenzene remain uncrosslinked and have an appropriate degree of branching. Such copolymers or their manufacturing methods are known in the above patent documents. It is preferable that the copolymer dissolves in an amount of 50 g or more in 100 g of solvent. More preferably, the copolymer dissolves in an amount of 80 g or more.

[0060] The polyfunctional vinyl aromatic copolymer of the present invention may have a haze value (turbidity) of 0.1 or less in a toluene solution. Here, the haze value refers to the haze value measured by dissolving 0.5 g of the polyfunctional vinyl aromatic copolymer in 100 g of toluene in a quartz cell and measuring the haze value using an integrating sphere type light transmittance measuring device with toluene as a reference sample. The haze value is also related to the evaluation of solubility in a solvent, and a low haze value means excellent solubility or less gel.

[0061] The third polyfunctional vinyl aromatic copolymer of the present invention will now be described.

[0062] The polyfunctional vinyl aromatic copolymer of the present invention contains a structural unit (a) derived from a divinyl aromatic compound, a structural unit (b) derived from a monovinyl aromatic compound having no substituent at the α-position, and a structural unit (c) derived from an α,α-disubstituted olefin compound. At least a part of the structural unit (a) contains the crosslinked structural unit (a2) represented by the above formula (2) and the vinyl group-containing structural unit (a1) represented by the above formula (1). The molar fraction (also referred to as the degree of crosslinking) of the crosslinked structural unit (a2) derived from a divinyl aromatic compound to the structural unit (a) is in the range of 0.05 to 0.60, and the molar fraction of the vinyl group-containing structural unit (a1) to the total of the structural units (a), (b) and (c) is in the range of 0.001 to 0.60.

[0063] The crosslinking degree of the crosslinking structural unit (a2) is in the range of 0.05 to 0.60, with a preferred lower limit of 0.06, and more preferably 0.07. The preferred upper limit is 0.55, and more preferably 0.50. Particularly preferably 0.45, and most preferably 0.40. The optimum range is 0.20 to 0.40. According to the method for producing the polyfunctional vinyl aromatic copolymer of the present invention, the crosslinking degree and the vinyl group-containing structural unit (a1) represented by formula (1) are parameters that can be independently controlled and changed arbitrarily. However, if the crosslinking degree of the crosslinking structural unit (a2) is less than 0.05, the crosslinking degree of the polyfunctional vinyl aromatic copolymer is small, and therefore the crosslinking reaction within the molecule of the vinyl group-containing structural unit (a1) represented by formula (1) is likely to occur, and microgels tend to be formed during copolymerization with a conjugated diene compound or the like. On the other hand, if it is greater than 0.60, the molecular weight of the polyfunctional vinyl aromatic copolymer itself increases, and the molecular weight distribution tends to broaden, so that the abrasion resistance tends to decrease.

[0064] The structural unit (a) derived from a divinyl aromatic compound may have several different structures, such as one in which only one vinyl group has reacted and one in which two vinyl groups have reacted, but the vinyl-group-containing structural unit (a1) represented by the above formula (1), which is a structural unit having a structure in which only one vinyl group has reacted, is contained in the above molar fraction in the range of 0.001 to 0.60. The preferred lower limit is 0.005, more preferably 0.01. The preferred upper limit is 0.55, more preferably 0.50. The optimum range is 0.10 to 0.50. By setting the molar fraction within the above range, it is possible to obtain a copolymer rubber that has excellent reactivity during copolymerization with a conjugated diene compound while maintaining solubility, has excellent compatibility with diene rubber, and is also excellent in processability, tensile strength, and abrasion resistance. If the molar fraction is less than 0.001, the copolymerization reactivity with a conjugated diene compound, etc. tends to decrease, and if it is greater than 0.60, microgels tend to be generated during copolymerization. Here, the above molar fraction is the molar fraction of the vinyl group-containing structural unit (a1) relative to the total of the structural units (a), (b) and (c), and is calculated by the following formula (33). (a1) / [(a)+(b)+(c)] (33) Here, (a), (b), (c) and (a1) indicate the amounts (moles) of the structural units (a), (b), (c) and (a1), respectively.

[0065] The polyfunctional vinyl aromatic copolymer of the present invention contains 0.5 to 60 mol % of the structural unit (a) derived from a divinyl aromatic compound. When the structural units are composed only of the structural units (a), (b), and (c), the molar fraction of the structural unit (a) is 0.005 to 0.75 relative to the sum of the structural units (a), (b), and (c). This molar fraction is calculated by the following formula (34). (a) / [(a)+(b)+(c)] (34) (Here, (a), (b) and (c) are defined as the same as in formula (33).) The lower limit of the molar fraction is preferably 0.006, more preferably 0.007, and the upper limit is preferably 0.70, more preferably 0.60. The optimum range is 0.10 to 0.55. In the case where structural units other than the structural units (a), (b) and (c) are contained, the lower limit of the content is preferably 0.2 mol%, more preferably 0.5 mol%, and even more preferably 0.7 mol%, and the upper limit is preferably 50 mol%, more preferably 45 mol%, and even more preferably 40 mol%.

[0066] The polyfunctional vinyl aromatic copolymer of the present invention contains 5.0 to 75 mol % of structural units (b) derived from a monovinyl aromatic compound having no substituent at the α-position. In terms of molar fraction, it is 0.05 to 0.75. A preferred lower limit is 0.06. A more preferred lower limit is 0.07. A preferred upper limit is 0.70, more preferably 0.65. Optimally, it is 0.30 to 0.60.

[0067] When the polymer consists of only the structural units (a), (b), and (c), the molar fraction of the structural unit (b) is calculated by the following formula (35). (b) / [(a)+(b)+(c)] (35) (Here, (a), (b) and (c) are defined as the same as in formula (33).) Even when structural units other than the structural units (a), (b) and (c) are contained, the molar fraction of the structural unit (b) is preferably within the above range.

[0068] The polyfunctional vinyl aromatic copolymer of the present invention contains 5.0 to 75 mol % of structural units (c) derived from an α,α-disubstituted olefin compound. In terms of molar fraction, it is 0.05 to 0.75. A preferred lower limit is 0.06. A more preferred lower limit is 0.07. A preferred upper limit is 0.70, more preferably 0.65. Optimally, it is 0.10 to 0.40.

[0069] When the polymer consists only of the structural units (a), (b), and (c), the mole fraction of the structural unit (c) is calculated by the following formula (36). (c) / [(a)+(b)+(c)] (36) (Here, (a), (b) and (c) are defined as the same as in formula (33).) Even when structural units other than the structural units (a), (b) and (c) are contained, the molar fraction of the structural unit (c) is preferably within the above range.

[0070] The structural unit (a) derived from a divinyl aromatic compound contains a vinyl group as a branching component for expressing copolymerization reactivity with a conjugated diene compound, while the structural unit (b) derived from a monovinyl aromatic compound that does not have a substituent at the α-position does not have a vinyl group involved in the curing reaction, and thus provides moldability, compatibility, etc. The structural unit (c) derived from an α,α-disubstituted olefin compound is prone to chain transfer reactions, and therefore has the function of controlling molecular weight. Furthermore, if the molar fraction of the structural unit (a) is less than 0.005, the heat resistance of the cured product is insufficient, and if it exceeds 0.75, the molding processability is reduced. If the molar fraction of the structural unit (b) is more than 0.75, the heat resistance is reduced, and if it is less than 0.05, the molding processability is reduced. On the other hand, if the molar fraction of the structural unit (c) is more than 0.75, the heat resistance is reduced, and if it is less than 0.05, the molecular weight increases, and the compatibility with other resins and the molding processability are reduced.

[0071] The polyfunctional vinyl aromatic copolymer of the present invention may contain other structural units in addition to the above structural units, the details of which will be understood from the explanation of the production method.

[0072] The Mn (number average molecular weight in terms of standard polystyrene measured by gel permeation chromatography) of the polyfunctional vinyl aromatic copolymer of the present invention is 300 to 50,000, preferably 500 to 45,000, more preferably 600 to 40,000. It is further preferably 700 to 35,000, and most preferably 800 to 30,000. It is optimally 900 to 3,000. If Mn is less than 300, the amount of monofunctional copolymer contained in the copolymer increases, so that the copolymerization reactivity with the conjugated diene compound tends to decrease, and if it exceeds 50,000, gel tends to be easily generated, and moldability and tensile elongation at break tend to decrease. The molecular weight distribution is 10.0 or less, preferably 9.0 or less, more preferably 1.3 to 8.0. It is optimally 2.0 to 6.0. If Mw / Mn exceeds 10.0, the processability of the copolymer rubber tends to deteriorate, and gel tends to be generated.

[0073] The polyfunctional vinyl aromatic copolymer of the present invention is soluble in a solvent selected from toluene, xylene, tetrahydrofuran, dichloroethane, or chloroform, and is preferably soluble in any of the above solvents. In order to be a solvent-soluble, polyfunctional copolymer, it is necessary that a portion of the vinyl groups of divinylbenzene remain uncrosslinked and have an appropriate degree of branching. Such copolymers or their manufacturing methods are known in the above patent documents. It is preferable that the copolymer dissolves in an amount of 50 g or more in 100 g of solvent. More preferably, the copolymer dissolves in an amount of 80 g or more.

[0074] Next, the first, second and third methods for producing the polyfunctional vinyl aromatic copolymers of the present invention will be described. By using these methods, the polyfunctional vinyl aromatic copolymers of the present invention can be advantageously produced.

[0075] In the production method of the present invention, polymerization raw materials including essential components such as a divinyl aromatic compound and a monovinyl aromatic compound may be dissolved in a homogeneous solvent having a dielectric constant of 2.0 to 15.0, and polymerized in the presence of a Lewis acid catalyst at a temperature of 20 to 60°C.

[0076] The divinylaromatic compound makes the copolymer branched and multifunctional, and also plays an important role as a cross-linking component for generating branches when the copolymer is copolymerized with a conjugated diene compound. Examples of the divinylaromatic compound preferably used are divinylbenzene (including each isomer), divinylnaphthalene (including each isomer), and divinylbiphenyl (including each isomer), but are not limited thereto. These can be used alone or in combination of two or more kinds. From the viewpoint of moldability, divinylbenzene (m-isomer, p-isomer, or a mixture of these isomers) is more preferable.

[0077] The monovinyl aromatic compound improves the solvent solubility, compatibility, and processability of the copolymer. Examples of monovinyl aromatic compounds include vinyl aromatic compounds such as styrene, vinylnaphthalene, and vinylbiphenyl; o-methylstyrene, m-methylstyrene, p-methylstyrene, o,p-dimethylstyrene, o-ethylvinylbenzene, m-ethylvinylbenzene, and p-ethylvinylbenzene; and other nuclear alkyl-substituted vinyl aromatic compounds. In order to prevent gelation of the copolymer and improve solubility, compatibility, and processability in a solvent, styrene, ethylvinylbenzene (including each isomer), ethylvinylbiphenyl (including each isomer), and ethylvinylnaphthalene (including each isomer) are particularly preferred from the viewpoints of cost and availability. From the viewpoints of compatibility and cost, styrene and ethylvinylbenzene (m-isomer, p-isomer, or a mixture of these isomers) are more preferred. Those having no substituent at the α-position are preferred.

[0078] In the first invention, the cycloolefin monomer contains an aromatic condensed ring structure, which also acts as a chain transfer agent and controls the molecular weight and molecular weight distribution of the copolymer during polymerization, thereby improving the solvent solubility and processability while maintaining the high dielectric properties of the hydrocarbon resin material. The cycloolefin monomer may be a monomer consisting of an aromatic ring and a cycloolefin ring condensed therewith, and the cycloolefin ring may have an unsaturated bond capable of cationic polymerization, and may contain heteroatoms such as oxygen and sulfur atoms as ring-constituting atoms. The aromatic ring and the cycloolefin ring may have a substituent such as an alkyl group, an alkoxy group, or an acyl group. Preferred cycloolefin monomers include monomers selected from the group consisting of indene compounds, acenaphthylene compounds, benzofuran compounds, and benzothiophene compounds.

[0079] The indene-based compound may be at least one compound selected from the group consisting of indene, alkyl indenes, halogenated indenes, aryl indenes, alkoxy indenes, alkoxy carbonyl indenes, acyloxy indenes, alkyl silyl indenes, and alkyl stannyl indenes. The acenaphthylene-based compound may include at least one compound selected from the group consisting of acenaphthylene, alkylacenaphthylenes, halogenated acenaphthylenes, arylacenaphthylenes, alkoxyacenaphthylenes, alkoxycarbonylacenaphthylenes, acyloxyacenaphthylenes, alkylsilylacenaphthylenes, and alkylstannylacenaphthylenes. The benzofuran-based compounds and benzothiophene-based compounds may be benzofurans and benzothiophenes modified with the same substituents as indene-based compounds and acenaphthylene-based compounds, in addition to benzofuran and benzothiophene. The benzofuran-based compounds may be 1-benzofuran or 2-benzofuran. The same applies to benzothiophene.

[0080] The cycloolefin monomers specifically exemplified above can be used alone or in combination of two or more. Among these cycloolefin monomers, indene compounds and acenaphthylene compounds are preferably used from the viewpoints of industrial availability, dielectric properties, and high molecular weight control effect of the copolymer of the present invention. Most preferably, indene is used from the viewpoints of copolymerization reactivity and high molecular weight control effect.

[0081] In the third invention, the α,α-disubstituted olefin compound has the function of controlling the molecular weight of the copolymer, and therefore improves the solvent solubility, compatibility, and processability. Examples of the α,α-disubstituted olefin compound include, but are not limited to, one or more monomers selected from the group consisting of isobutylene, diisobutylene, 2-methyl-1-butene, 2-methyl-1-pentene, 1-methyl-1-cyclopentene, 2-methyl-1-hexene, 1-methyl-1-cyclohexene, 2-methyl-1-heptene, 2-methyl-1-octene, 2-methyl-1-nonene, 2-methyl-1-decene, 2-methyl-1-dodecene, 2-methyl-1-tetradecene, 2-methyl-1-hexadecene, 2-methyl-1-octadecene, 2-methyl-1-eicosene, 2-methyl-1-docosene, 2-methyl-1-tetracosene, and α-methylstyrene. In order to control the molecular weight and molecular weight distribution of the copolymer, prevent the generation of gel, and improve the solubility in solvents, compatibility, and processability, an α,α-disubstituted olefin compound substituted with an aliphatic group, such as isobutylene, diisobutylene, 2-methyl-1-pentene, 2-methyl-1-hexene, and isoprene, or an α,α-disubstituted olefin compound substituted with an aromatic group, such as α-methylstyrene, can be preferably used from the viewpoints of cost and availability. From the viewpoints of ease of production and cost, isobutylene, diisobutylene, and α-methylstyrene are more preferable.

[0082] In the method for producing the copolymer of the present invention, in addition to the essential components such as the divinyl aromatic compound and the monovinyl aromatic compound, other monomers such as trivinyl aromatic compounds, trivinyl aliphatic compounds, divinyl aliphatic compounds and monovinyl aliphatic compounds can be used to introduce structural units (e) derived from the other monomers into the copolymer, within the scope not impairing the effects of the present invention.

[0083] Specific examples of the other monomers include, but are not limited to, 1,3,5-trivinylbenzene, 1,3,5-trivinylnaphthalene, 1,2,4-trivinylcyclohexane, ethylene glycol diacrylate, butadiene, etc. These can be used alone or in combination of two or more. The other monomers are preferably used in an amount of less than 30 mol% of the total monomers. Thereby, the structural unit (e) derived from the other monomers is set to a range of less than 30 mol% of the total amount of structural units in the copolymer.

[0084] In the method for producing the copolymer of the present invention, the copolymer is produced by polymerizing essential components such as a divinyl aromatic compound and a monovinyl aromatic compound, and optionally further containing other monomers, in the presence of a Lewis acid catalyst.

[0085] In the first invention, the proportion of each monomer component used is preferably within the following range relative to 100 mol % in total of the divinyl aromatic compound, the monovinyl aromatic compound, and the cycloolefin monomer. Divinyl aromatic compound: 5 to 35 mol %, preferably 6 to 30 mol %, more preferably 7 to 25 mol %. Monovinyl aromatic compound: 5 to 25 mol %, preferably 6 to 23 mol %, more preferably 7 to 20 mol %. Cycloolefin monomer: 40 to 90 mol %, preferably 45 to 86 mol %, more preferably 50 to 80 mol %.

[0086] In the second invention, the proportion of each component serving as a monomer is preferably within the following range relative to 100 mol % in total of the divinyl aromatic compound and the monovinyl aromatic compound. Divinyl aromatic compound: 0.2 to 45 mol %, preferably 0.3 to 40 mol %, more preferably 0.4 to 35 mol %. Monovinyl aromatic compound: 55 to 99.8 mol %, preferably 60 to 99.7 mol %, more preferably 65 to 99.6 mol %.

[0087] In the third invention, the proportion of each monomer component is preferably within the following range relative to 100 mol % in total of the divinyl aromatic compound, the monovinyl aromatic compound having no substituent at the α-position, and the α,α-disubstituted olefin compound. Divinyl aromatic compound: 0.2 to 75 mol %, preferably 0.3 to 65 mol %, more preferably 0.4 to 55 mol %, optimally 5 to 50 mol %. Monovinyl aromatic compound not having a substituent at the α-position: 7 to 99 mol %, preferably 10 to 95 mol %, more preferably 15 to 90 mol %. α,α-disubstituted olefin compound: 5 to 99 mol %, preferably 10 to 95 mol %, more preferably 15 to 90 mol %, optimally 20 to 60 mol %.

[0088] The Lewis acid catalyst (e) used here is a compound consisting of a metal ion (acid) and a ligand (base), and can be used without any particular limitation as long as it is capable of accepting an electron pair. Among the Lewis acid catalysts, metal fluorides or complexes thereof are preferred from the viewpoint of thermal decomposition resistance of the resulting copolymer, and in particular, divalent to hexavalent metal fluorides or complexes thereof such as B, Al, Ga, In, Si, Ge, Sn, Pb, Sb, Bi, Ti, W, Zn, Fe, and V are preferred. These catalysts can be used alone or in combination of two or more kinds. From the viewpoint of controlling the molecular weight and molecular weight distribution of the resulting copolymer and the polymerization activity, an ether complex of boron trifluoride is most preferably used. Here, examples of the ether complex include diethyl ether and dimethyl ether.

[0089] The Lewis acid catalyst is preferably used in the range of 0.001 to 100 moles, more preferably 0.01 to 50 moles, relative to 100 moles of the total of all monomer components. Most preferably 0.1 to 10 moles. If it exceeds 100 moles, the polymerization rate becomes too high, making it difficult to control the molecular weight distribution. If it is less than 0.001 moles, the polymerization rate becomes too low, resulting in an increase in costs and making it unsuitable for industrial implementation.

[0090] In the process for producing the copolymer of the present invention, one or more Lewis base compounds may be used as co-catalysts, if desired. Specific examples of the Lewis base compound include the following compounds. 1) Ester compounds such as ethyl acetate, butyl acetate, phenyl acetate, and methyl propionate, 2) Thioester compounds such as methyl mercaptopropionic acid and ethyl mercaptopropionic acid, 3) Ketone compounds such as methyl ethyl ketone, methyl isobutyl ketone, and benzophenone, 4) Amine compounds such as methylamine, ethylamine, propylamine, butylamine, cyclohexylamine, methylethylamine, dimethylamine, diethylamine, dipropylamine, and dibutylamine; 5) Ether compounds such as diethyl ether and tetrahydrorane, 6) Thioether compounds such as diethyl sulfide and diphenyl sulfide, and 7) Phosphine compounds such as tripropylphosphine, tributylphosphine, trihexylphosphine, tricyclohexylphosphine, trioctylphosphine, vinylphosphine, propenylphosphine, cyclohexenylphosphine, dialkenylphosphine, and trialkenylphosphine. Among these, ester compounds and ketone compounds are preferably used because they act synergistically with the Lewis acid catalyst and can easily control the polymerization rate and the molecular weight distribution of the polymer. These Lewis base compounds can be used alone or in combination.

[0091] The Lewis base compound, which is a cocatalyst component, coordinates with the Lewis acid catalyst, which is a counter anion, during polymerization reaction, thereby controlling the interaction between the carbocation, which is an active species, and the counter anion, thereby adjusting the relative reaction frequency between the cycloolefin compound, which functions as a chain transfer agent, and the divinyl aromatic compound and the monovinyl aromatic compound.Usually, by adding the Lewis base compound, the interaction between the carbocation, which is an active species, and the counter anion is strengthened, so that the divinyl aromatic compound and the monovinyl aromatic compound are prevented from causing excessive insertion reaction, and the chain transfer reaction after the insertion reaction of the cycloolefin compound is easily caused, making it easy to control the molecular weight.

[0092] The amount of the Lewis base compound as the co-catalyst is preferably 0.005 to 500 mol, more preferably 0.01 to 100 mol, and more preferably 0.1 to 50 mol, per 100 mol of the total of all monomers. Within the above range, the polymerization rate is appropriately maintained and at the same time, the selectivity of the reaction between the monomers is improved, resulting in excellent productivity and suppressing excessive increase or decrease in molecular weight, thereby obtaining a copolymer with excellent moldability.

[0093] The polymerization reaction is carried out by cationic copolymerization at a temperature of 20 to 120° C. in a homogeneous solvent in which the polymerization raw materials containing the above-mentioned monomer mixture and Lewis acid catalyst are dissolved in a solvent having a dielectric constant of 2.0 to 15.0.

[0094] The solvent is a compound that does not essentially inhibit cationic polymerization, and dissolves the catalyst, polymerization additive, cocatalyst, monomer, and the vinyl aromatic copolymer to be produced to form a homogeneous solution, and is preferably an organic solvent having a dielectric constant in the range of 2.0 to 15.0, and may be used alone or in combination of two or more. If the dielectric constant of the solvent is less than 2.0, the molecular weight distribution becomes broad, which is not preferable, and if it exceeds 15.0, the polymerization rate decreases.

[0095] As the organic solvent, toluene, xylene, n-hexane, cyclohexane, methylcyclohexane or ethylcyclohexane are particularly preferred from the viewpoint of the balance between polymerization activity and solubility. The amount of the solvent used is determined so that the concentration of the copolymer in the polymerization solution at the end of polymerization is 1 to 90 wt%, preferably 10 to 80 wt%, and particularly preferably 20 to 70 wt%, taking into consideration the viscosity of the resulting polymerization solution and the ease of heat removal. If the concentration is less than 1 wt%, the polymerization efficiency is low, leading to an increase in costs, and if it exceeds 90 wt%, the molecular weight and molecular weight distribution increase, leading to a decrease in moldability.

[0096] When producing a soluble polyfunctional vinyl aromatic polymer, it is necessary to carry out the polymerization at a temperature of 20 to 120° C., preferably 40 to 100° C. If the polymerization temperature exceeds 120° C., the selectivity of the reaction decreases, resulting in problems such as an increase in molecular weight distribution and the generation of gel, while if the polymerization is carried out at a temperature below 20° C., the catalytic activity decreases significantly, making it necessary to add a large amount of catalyst.

[0097] After the polymerization reaction has been stopped, the method for recovering the copolymer is not particularly limited, and for example, a commonly used method such as a heat concentration method, a steam stripping method, or precipitation in a poor solvent may be used.

[0098] The polyfunctional vinyl aromatic copolymer obtained by the above-mentioned production method contains the structural unit (a) derived from a divinyl aromatic compound, the structural unit (b) derived from a monovinyl aromatic compound, and the structural unit (c) derived from a cycloolefin monomer containing an aromatic condensed ring structure, and at least a part of the structural unit (a) derived from a divinyl aromatic compound exists as the vinyl group-containing structural unit (a1) represented by the above formula (1).The copolymer is soluble in toluene, xylene, tetrahydrofuran, dichloroethane or chloroform.

[0099] The first, second and third polyfunctional vinyl aromatic copolymers of the present invention have unreacted vinyl groups, so they may be polymerized and cured by themselves and molded, but they are preferably copolymerized with other polymerizable resins or monomers to obtain a second copolymer.In particular, the polyfunctional vinyl aromatic copolymers of the present invention are excellent for obtaining a conjugated diene-based copolymer (rubber) by copolymerizing with other monomers including conjugated dienes.

[0100] The above-mentioned polyfunctional vinyl aromatic copolymer (A) of the present invention is copolymerized with 1) a conjugated diene compound (B), or 2) a conjugated diene compound (B) and an aromatic vinyl compound (C) as raw materials to obtain the conjugated diene copolymer of the present invention. When the aromatic vinyl compound (C) is not used, a diene rubber such as butadiene rubber or isoprene rubber can be obtained, and when the aromatic vinyl compound (C) is used, a conjugated diene copolymer such as SBR can be obtained. This conjugated diene copolymer exhibits the properties of rubber, so it is also called copolymer rubber.

[0101] In the polymerization step for obtaining a conjugated diene copolymer, there are a method (Method I) in which the polyfunctional vinyl aromatic copolymer (A) of the present invention is reacted with an organolithium compound to prepare a polyfunctional anionic polymerization initiator in advance in a specified reactor, and the polyfunctional anionic polymerization initiator is supplied to a reactor in which a conjugated diene compound is polymerized to carry out a polymerization or copolymerization reaction; a method (Method II) in which a raw material containing the polyfunctional vinyl aromatic copolymer (A) and a conjugated diene compound (B), or the polyfunctional vinyl aromatic copolymer (A), a conjugated diene compound (B) and an aromatic vinyl compound (C), and an organolithium compound (or an anionic polymerization initiator) is reacted with a raw material containing the polyfunctional vinyl aromatic copolymer (A) and a conjugated diene compound (B) and an aromatic vinyl compound (C) to carry out a copolymerization reaction. and a method (Method II) in which the conjugated diene compound (B) or the conjugated diene compound (B) and the aromatic vinyl compound (C) are supplied to a reactor at once to carry out a copolymerization reaction. Furthermore, a method (Method III) in which the conjugated diene compound (B) or the conjugated diene compound (B) and the aromatic vinyl compound (C) are supplied to a reactor to polymerize the conjugated diene compound or copolymerize the conjugated diene compound and the aromatic vinyl compound, and the polymer of the conjugated diene compound having an active end produced in the reactor or the copolymer of the conjugated diene compound and the aromatic vinyl compound is reacted with the polyfunctional vinyl aromatic copolymer (A) to synthesize a conjugated diene copolymer can be employed. Among these polymerization methods, method I is preferred in terms of the efficiency of the copolymerization reaction with the polyfunctional vinyl aromatic copolymer (A) of the present invention.

[0102] Examples of the conjugated diene compound (B) include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 3-methyl-1,3-pentadiene, 1,3-heptadiene, and 1,3-hexadiene. Among these, 1,3-butadiene and isoprene are preferred. These may be used alone or in combination of two or more.

[0103] As the aromatic vinyl compound (C), styrene, α-methylstyrene, 1-vinylnaphthalene, 3-vinyltoluene, ethylvinylbenzene, vinylxylene, 4-cyclohexylstyrene, 2,4,6-trimethylstyrene, tert-butoxydimethylsilylstyrene, isopropoxydimethylsilylstyrene, and the like can be used alone or in combination of two or more kinds, with styrene being particularly preferred.

[0104] When 1,3-butadiene is used as the conjugated diene compound (B) and styrene is used as the aromatic vinyl compound, so-called styrene-butadiene rubber (SBR) is obtained. When styrene is not used as the aromatic vinyl compound and 1,3-butadiene is used as the conjugated diene compound (B), so-called butadiene rubber (BR) is obtained. When isoprene is used as the conjugated diene compound (B) and there is no structural unit of the aromatic vinyl compound (C), the result is isoprene rubber (IR). Among them, the styrene-butadiene rubber (SBR) structure is particularly preferred because it has excellent abrasion resistance, heat resistance, and aging resistance.

[0105] The organolithium compound used as the initiator is not particularly limited, and examples thereof include mono-organolithium compounds such as n-butyllithium, sec-butyllithium, tert-butyllithium, n-propyllithium, iso-propyllithium, and benzyllithium; and polyfunctional organolithium compounds such as 1,4-dilithiobutane, 1,5-dilithiopentane, 1,6-dilithiohexane, 1,10-dilithiodecane, 1,1-dilithiodiphenylene, dilithiopolybutadiene, dilithiopolyisoprene, 1,4-dilithiobenzene, 1,2-dilithio-1,2-diphenylethane, 1,4-dilithio-2-ethylcyclohexane, 1,3,5-trilithiobenzene, and 1,3,5-trilithio-2,4,6-triethylbenzene. Among these, the mono-organolithium compounds of n-butyllithium, sec-butyllithium, and tert-butyllithium are preferred.

[0106] When producing a conjugated diene copolymer, it is preferable to add the following polar compounds as vinylating agents for controlling the microstructure of the conjugated diene portion and for the purpose of improving the polymerization rate. Examples of polar compounds include ethers such as tetrahydrofuran, diethyl ether, dioxane, ethylene glycol dimethyl ether, ethylene glycol dibutyl ether, diethylene glycol dimethyl ether, diethylene glycol dibutyl ether, dimethoxybenzene, and 2,2-bis(2-oxolanyl)propane; tertiary amine compounds such as tetramethylethylenediamine, dipiperidinoethane, trimethylamine, triethylamine, pyridine, and quinuclidine; alkali metal alkoxide compounds such as potassium tert-amylate, potassium tert-butylate, sodium tert-butylate, and sodium tert-amylate; and phosphine compounds such as triphenylphosphine. These polar compounds may be used alone or in combination of two or more. The amount of the polar compound used is selected depending on the purpose and effect of the resulting conjugated diene copolymer composition, but is preferably 0.005 to 100 mol per 1 mol of the organolithium compound as the initiator.

[0107] The conjugated diene copolymer is preferably polymerized in a predetermined solvent. In particular, it is preferably polymerized in a solvent that satisfies the above-mentioned dielectric constant. The solvent is not particularly limited, and for example, a hydrocarbon-based solvent such as a saturated hydrocarbon or an aromatic hydrocarbon is used. Specific examples of the solvent include aliphatic hydrocarbons such as butane, pentane, hexane, and heptane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclopentane, and methylcyclohexane; aromatic hydrocarbons such as benzene, toluene, and xylene, and hydrocarbon-based solvents consisting of mixtures thereof. The above-mentioned conjugated diene compound and polymerization solvent are preferably treated with an organometallic compound, either alone or in the form of a mixture thereof. This allows the allenes and acetylenes contained in the conjugated diene compound and polymerization solvent to be treated. As a result, a polymer having a high concentration of active terminals can be obtained, and a high modification rate can be achieved.

[0108] The polymerization active terminals of the conjugated diene copolymer of the present invention can be further reacted with a modifier. In this specification, the conjugated diene copolymer obtained by this reaction is also referred to as a modified conjugated diene copolymer.

[0109] The modifier used in this embodiment (also referred to as "terminal modifier") is a compound having a functional group capable of reacting with the polymerization active terminal of the conjugated diene copolymer. The terminal modifier is not particularly limited, but when a monofunctional compound is used, a linear both-end-modified diene copolymer is obtained, and when a polyfunctional compound is used, a branched both-end-modified diene copolymer is obtained. Preferably, a monofunctional or polyfunctional compound containing at least one element selected from the group consisting of nitrogen, silicon, tin, phosphorus, oxygen, sulfur, and halogen is used as the terminal modifier. In addition, a terminal modifier containing an onium generating agent is added and reacted to introduce an onium structure into the modified conjugated diene copolymer. In addition, a terminal modifier containing a plurality of functional groups containing these elements in the molecule, or a terminal modifier containing a functional group containing a plurality of these elements, can also be used. By the process of continuously adding these terminal modifiers, for example, when molded into a vehicle tire or other such product, a vulcanized rubber composition tends to be obtained that has lower rolling resistance, excellent wear resistance, tensile strength, and tear strength.

[0110] Various terminal modifying agents that can be used in the present invention will be described below, although they are not limited to the examples given.

[0111] Examples of the nitrogen-containing compound as the terminal modifying agent include isocyanate compounds, isothiocyanate compounds, isocyanuric acid derivatives, nitrogen-containing carbonyl compounds, nitrogen-containing vinyl compounds, and nitrogen-containing epoxy compounds. Examples of silicon-containing compounds as terminal modifying agents include halogenated silicon compounds, epoxydized silicon compounds, vinylated silicon compounds, alkoxy silicon compounds, and alkoxy silicon compounds containing a nitrogen-containing group.

[0112] Examples of the tin-containing compound as the terminal modifier include halogenated tin compounds and organic tin carboxylate compounds. Examples of the phosphorus-containing compound as the terminal modifier include phosphorous ester compounds and phosphino compounds. Examples of the oxygen-containing compound as the terminal modifier include epoxy compounds, ether compounds, and ester compounds. Examples of the sulfur-containing compound as the terminal modifier include mercapto group derivatives, thiocarbonyl compounds, and isothiocyanates. Examples of the halogen-containing compound as the terminal modifier include the above-mentioned halogenated silicon compounds and halogenated tin compounds.

[0113] Examples of the onium generator as the terminal modifying agent include a protected amine compound (which generates ammonium) capable of forming a primary or secondary amine, a protected phosphine compound (which generates phosphonium) capable of forming hydrophosphine, and a compound (which generates oxonium or sulfonium) capable of forming a hydroxyl group or a thiol. It is preferable to use a terminal modifying agent having a functional group for bonding the onium generator and the modified conjugated diene polymer in the molecule. Examples of the functional group for bonding the modified conjugated diene polymer include unsaturated groups such as carbonyl groups (ketones, esters, etc.), vinyl groups, epoxy groups, halogenated silicon groups, and alkoxy silicon groups.

[0114] Specific examples of the terminal modifying agent include isocyanate compounds such as 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, diphenylmethane diisocyanate, polymeric diphenylmethane diisocyanate (CMDI), phenyl isocyanate, isophorone diisocyanate, hexamethylene diisocyanate, butyl isocyanate, and 1,3,5-benzene triisocyanate. Examples of isocyanuric acid derivatives include 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate, 1,3,5-tris(3-triethoxysilylpropyl)isocyanurate, 1,3,5-tri(oxiran-2-yl)-1,3,5-triazinane-2,4,6-trione, 1,3,5-tris(isocyanatomethyl)-1,3,5-triazinane-2,4,6-trione, and 1,3,5-trivinyl-1,3,5-triazinane-2,4,6-trione.

[0115] Specific examples of the nitrogen group-containing carbonyl compound include 1,3-dimethyl-2-imidazolidinone, 1-methyl-3-ethyl-2-imidazolidinone, 1-methyl-3-(2-methoxyethyl)-2-imidazolidinone, N-methyl-2-pyrrolidone, N-methyl-2-piperidone, N-methyl-2-quinolone, 4,4'-bis(diethylamino)benzophenone, 4,4'-bis(dimethylamino)benzophenone, methyl-2-pyridyl ketone, Examples of the amides include methyl-4-pyridyl ketone, propyl-2-pyridyl ketone, di-4-pyridyl ketone, 2-benzoylpyridine, N,N,N',N'-tetramethylurea, N,N-dimethyl-N',N'-diphenylurea, N,N-methyl diethylcarbamate, N,N-diethylacetamide, N,N-dimethyl-N',N'-dimethylaminoacetamide, N,N-dimethylpicolinic acid amide, and N,N-dimethylisonicotinic acid amide.

[0116] Specific examples of nitrogen group-containing vinyl compounds include N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N-methylmaleimide, N-methylphthalimide, N,N-bistrimethylsilylacrylamide, morpholinoacrylamide, 3-(2-dimethylaminoethyl)styrene, (dimethylamino)dimethyl-4-vinylphenylsilane, 4,4'-vinylidenebis(N,N-dimethylaniline), 4,4'-vinylidenebis(N,N-diethylaniline), 1,1-bis(4-morpholinophenyl)ethylene, and 1-phenyl-1-(4-N,N-dimethylaminophenyl)ethylene.

[0117] Specific examples of nitrogen-containing epoxy compounds include N,N,N',N'-tetraglycidyl-1,3-bisaminomethylcyclohexane, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 4,4-methylene-bis(N,N-diglycidylaniline), 1,4-bis(N,N-diglycidylamino)cyclohexane, N,N,N',N'-tetraglycidyl-p-phenylenediamine, 4,4'-bis(diglycidylamino)benzophenone, 4-(4-glycidylpiperazine), bis(glycidyl)-(N,N-diglycidyl)aniline, 2-[2-(N,N-diglycidylamino)ethyl]-1-glycidylpyrrolidine, bis(glycidylmethylaniline), N,N'-diglycidyl-4-glycidyloxyaniline, 4,4'-diglycidyl-diphenylmethylamine, 4,4'-diglycidyl-dibenzylmethylamine, N,N-diglycidylaniline, N,N-diglycidylorthotoluidine, and N,N-diglycidylaminomethylcyclohexane.

[0118] Specific examples of halogenated silicon compounds include dibutyldichlorosilane, methyltrichlorosilane, dimethyldichlorosilane, methyldichlorosilane, trimethylchlorosilane, tetrachlorosilane, tris(trimethylsiloxy)chlorosilane, tris(dimethylamino)chlorosilane, hexachlorodisilane, bis(trichlorosilyl)methane, 1,2-bis(trichlorosilyl)ethane, 1,2-bis(methyldichlorosilyl)ethane, 1,4-bis(trichlorosilyl)butane, and 1,4 bis(methyldichlorosilyl)butane.

[0119] Specific examples of the epoxidized silicon compound include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and epoxy-modified silicone.

[0120] Specific examples of alkoxysilicon compounds include tetramethoxysilane, tetraethoxysilane, triphenoxymethylsilane, and methoxy-substituted polyorganosiloxane.

[0121] Specific examples of alkoxysilicon compounds containing nitrogen-containing groups include 3-dimethylaminopropyltrimethoxysilane, 3-dimethylaminopropylmethyldimethoxysilane, 3-diethylaminopropyltriethoxysilane, 3-morpholinopropyltrimethoxysilane, 3-piperidinopropyltriethoxysilane, 3-hexamethyleneiminopropylmethyldiethoxysilane, 3-(4-methyl-1-piperazino)propyltriethoxysilane, 1-[3-(triethoxysilyl)-propyl]-3-methylhexahydropyrimidine, 3-(4 -Trimethylsilyl-1-piperazino)propyltriethoxysilane, 3-(3-triethylsilyl-1-imidazolidinyl)propylmethyldiethoxysilane, 3-(3-trimethylsilyl-1-hexahydropyrimidinyl)propyltrimethoxysilane, 3-dimethylamino-2-(dimethylaminomethyl)propyltrimethoxysilane, bis(3-dimethoxymethylsilylpropyl)-N-methylamine, bis(3-trimethoxysilylpropyl)-N-methylamine, bis(3-triethoxysilylpropyl)methylamine, tris( Trimethoxysilyl)amine, tris(3-trimethoxysilylpropyl)amine, N,N,N',N'-tetra(3-trimethoxysilylpropyl)ethylenediamine, 3-isocyanatopropyltrimethoxysilane, 3-cyanopropyltrimethoxysilane, 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-diethoxy-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-dimethoxy-1-(4-trimethoxysilylbutyl)-1-aza aza-2-silacyclohexane, 2,2-dimethoxy-1-(3-dimethoxymethylsilylpropyl)-1-aza-2-silacyclopentane, 2,2-dimethoxy-1-phenyl-1-aza-2-silacyclopentane, 2,2-diethoxy-1-butyl-1-aza-2-silacyclopentane, 2,2-dimethoxy-1-methyl-1-aza-2-silacyclopentane, 2,2-dimethoxy-8-(4-methylpiperazinyl)methyl-1,6-dioxa-2-silacyclooctane, 2,2-dimethoxy-8-(N,N-diethylamino)methyl-1,6-dioxa-2-silacyclooctane, etc.

[0122] Specific examples of the protected amine compound capable of forming a primary or secondary amine and having an unsaturated bond and a protected amine in the molecule include 4,4'-vinylidenebis[N,N-bis(trimethylsilyl)aniline], 4,4'-vinylidenebis[N,N-bis(triethylsilyl)aniline], 4,4'-vinylidenebis[N,N-bis(t-butyldimethylsilyl)aniline], 4,4'-vinylidenebis[N-methyl-N-(trimethylsilyl)aniline], 4,4'-vinylidenebis[N-ethyl-N-(trimethylsilyl)aniline], 4,4'-vinylidenebis[N-methyl-N -(triethylsilyl)aniline], 4,4'-vinylidenebis[N-ethyl-N-(triethylsilyl)aniline], 4,4'-vinylidenebis[N-methyl-N-(t-butyldimethylsilyl)aniline], 4,4'-vinylidenebis[N-ethyl-N-(t-butyldimethylsilyl)aniline], 1-[4-N,N-bis(trimethylsilyl)aminophenyl]-1-[4-N-methyl-N-(trimethylsilyl)aminophenyl]ethylene, 1-[4-N,N-bis(trimethylsilyl)aminophenyl]-1-[4-N,N-dimethylaminophenyl]ethylene, and the like. Specific examples of the protected amine compound capable of forming a primary or secondary amine and a compound having an alkoxysilane and a protected amine in the molecule include N,N-bis(trimethylsilyl)aminopropyltrimethoxysilane, N,N-bis(trimethylsilyl)aminopropylmethyldimethoxysilane, N,N-bis(trimethylsilyl)aminopropyltriethoxysilane, N,N-bis(trimethylsilyl)aminopropylmethyldiethoxysilane, N,N-bis(trimethylsilyl)aminoethyltrimethoxysilane, N,N-bis(trimethylsilyl)aminoethylmethyldiethoxysilane, N,N-bis(triethylsilyl)aminopropylmethyldiethoxysilane, 3-(4-trimethylsilyl-1-piperazino)propyltriethoxysilane, 3-(3-triethylsilyl-1-imidazoline)propyltriethoxysilane, 3-(4-trimethylsilyl-1-piperazino)propyltriethoxysilane, 3-(3-triethylsilyl-1-imidazoline)propyltriethoxysilane, 3-(4-trimethylsilyl-1-imidazoline)propyltriethoxysilane, 3-(4-trimethylsilyl-1-imidazoline)propyltriethoxysilane, 3-(4-trimethylsilyl-1-imidazoline)propyltriethoxysilane, 3-(4-trimethylsilyl-1-imidazoline)propyltriethoxysilane, 3-(4-trimethylsilyl-1-imidazoline)propyltriethoxysilane, 3-(4-triethyl ... 2,2-Dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-Diethoxy-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-Dimethoxy-1-(4-trimethoxy ... Examples of such silacyclohexane include 2,2-dimethoxy-1-(3-dimethoxymethylsilylpropyl)-1-aza-2-silacyclohexane, 2,2-dimethoxy-1-(3-dimethoxymethylsilylpropyl)-1-aza-2-silacyclopentane, 2,2-dimethoxy-1-phenyl-1-aza-2-silacyclopentane, 2,2-diethoxy-1-butyl-1-aza-2-silacyclopentane, and 2,2-dimethoxy-1-methyl-1-aza-2-silacyclopentane.

[0123] Specific examples of tin halide compounds include tetrachlorotin, tetrabromotin, trichlorobutyltin, trichlorooctyltin, dibromodimethyltin, dichlorodibutyltin, chlorotributyltin, chlorotrioctyltin, chlorotriphenyltin, 1,2-bis(trichlorostannyl)ethane, 1,2-bis(methyldichlorostannyl)ethane, 1,4-bis(trichlorostannyl)butane, 1,4 bis(methyldichlorostannyl)butane, and the like.

[0124] Specific examples of the organotin carboxylate compound include ethyltin tristearate, butyltin trioctanoate, butyltin tristearate, butyltin trilaurate, and dibutyltin bisoctanoate.

[0125] Specific examples of the phosphite ester compound include trimethyl phosphite, tributyl phosphite, and triphenoxide phosphite.

[0126] Specific examples of phosphino compounds include protected phosphino compounds such as P,P-bis(trimethylsilyl)phosphinopropyltrimethoxysilane and P,P-bis(triethylsilyl)phosphinopropylmethylethoxysilane, 3-dimethylphosphinopropyltrimethoxysilane, and 3-diphenylphosphinopropyltrimethoxysilane.

[0127] Specific examples of the oxygen-containing compound include polyglycidyl ethers such as ethylene glycol diglycidyl ether and glycerin triglycidyl ether, polyepoxy compounds such as 1,4-diglycidylbenzene, 1,3,5-triglycidylbenzene, polyepoxidized liquid polybutadiene, epoxidized soybean oil and epoxidized linseed oil, and ester compounds such as dimethyl adipate, diethyl adipate, dimethyl terephthalate and diethyl terephthalate, which generate hydroxyl groups at the polymer terminals.

[0128] Specific examples of sulfur-containing compounds include protected thiol compounds such as S-trimethylsilylthiopropyltrimethoxysilane and S-triethylsilylthiopropylmethyldiethylsilane, S-methylthiopropyltrimethoxysilane, S-ethylthiopropylmethyldiethoxysilane, N,N-ethyldithiocarbamate, phenylisothiocyanate, phenyl-1,4-diisothiocyanate, hexamethylenediisothiocyanate, and butylisothiocyanate.

[0129] The amount of the terminal modifier used is preferably more than 0.5 equivalents and not more than 10 equivalents, more preferably more than 0.7 equivalents and not more than 5 equivalents, and even more preferably more than 1 equivalent and not more than 4 equivalents, relative to 1 equivalent of the living terminal of the conjugated diene copolymer. In the present embodiment, the amount of the living terminal of the conjugated diene polymer may be calculated from the amount of the organolithium compound used in the polymerization and the number of lithium atoms bonded to the organolithium compound, or may be calculated from the number average molecular weight of the obtained conjugated diene copolymer. The terminal modifying agent may be used alone or in combination of two or more kinds.

[0130] Considering processability and physical properties, the weight-average molecular weight (polystyrene equivalent) of the conjugated diene copolymer of the present invention is preferably 100,000 to 2,000,000, and more preferably 150,000 to 1,000,000. The weight-average molecular weight can be determined by measuring a chromatogram using GPC with a column filled with polystyrene gel and deriving a calibration curve using standard polystyrene.

[0131] Regarding the composition of the structural units of the conjugated diene copolymer of the present invention, when the aromatic vinyl compound (C) is not used, the ratio of the polyfunctional vinyl aromatic copolymer (A) to the conjugated diene compound (B) is preferably within the following range. The structural unit (A1) derived from the polyfunctional vinyl aromatic copolymer (A) is 0.001 to 6 weight %, preferably 0.001 to 5 weight %, more preferably 0.005 to 5 weight %, and even more preferably 0.01 to 5 weight %, and the structural unit (B1) derived from the conjugated diene compound (B) is 29 to 99.999 weight %, preferably 80 to 99.999 weight %, more preferably 90 to 99.995 weight %, and even more preferably 95 to 99.99 weight %.

[0132] When an aromatic vinyl compound (C) is used, the above proportions are preferably within the following ranges: the structural unit (A1) is within the same range as above, the structural unit (B1) is 30 to 97.999% by weight, preferably 45 to 94.995% by weight, and more preferably 55 to 89.99% by weight, the structural unit (C1) derived from the aromatic vinyl compound (C) is 2 to 50% by weight, preferably 5 to 45% by weight, and more preferably 10 to 40% by weight. In the case of a modified conjugated diene copolymer, the structural unit (H1) derived from the terminal modifier may be 1 to 0% by weight. When the structural unit (H1) is contained, the structural unit (H1) is excluded from the calculation of the above ratio. The structural unit (A1) imparts a branched structure to the conjugated diene copolymer, increases the molecular weight, and / or increases the amount of terminal modifier introduced, thereby improving the physical properties of the conjugated diene copolymer and / or improving the dispersibility of the reinforcing filler.

[0133] The microstructure (cis, trans, vinyl bond amount) of the conjugated diene copolymer can be arbitrarily changed by using a polar compound, etc., but the content of vinyl bonds (1,2-bonds) in the conjugated diene unit before the terminal is modified is preferably 10 to 80 mol%. When the conjugated diene copolymer of the present invention is made into a conjugated diene copolymer composition described later and further crosslinked to be used as an automobile tire, in order to highly balance the rolling resistance performance and the wear resistance, the content is preferably 20 to 75 mol%, more preferably 30 to 75 mol%, and even more preferably 40 to 70 mol%. At this time, the mass ratio of cis bonds and trans bonds in the conjugated diene bond unit is preferably cis bonds / trans bonds=1 / 1.1 to 1.5.

[0134] If necessary, a reaction terminator may be added to the polymer solution of the conjugated diene copolymer obtained by the above-mentioned polymerization method. Examples of the reaction terminator include alcohols such as methanol, ethanol, and propanol; organic acids such as stearic acid, lauric acid, and octanoic acid; and water.

[0135] After the polymerization reaction of the conjugated diene copolymer, metals contained in the polymer may be deashed as necessary. For example, the deashing method may involve contacting the polymer solution with water, an organic acid, an inorganic acid, an oxidizing agent such as hydrogen peroxide, etc. to extract the metals, and then separating the aqueous layer.

[0136] Furthermore, an antioxidant may be added to the polymer solution of the conjugated diene copolymer. Examples of the antioxidant include phenol-based stabilizers, phosphorus-based stabilizers, and sulfur-based stabilizers.

[0137] A conjugated diene copolymer can be obtained from a polymer solution by a conventionally known method, such as a method of separating the solvent by steam stripping or the like, filtering the polymer, and then dehydrating and drying the polymer to obtain the polymer, a method of concentrating the polymer in a flashing tank and then devolatilizing the polymer with a vent extruder or the like, or a method of directly devolatilizing the polymer with a drum dryer or the like.

[0138] The conjugated diene copolymer composition of the present invention preferably contains 0.5 to 200 parts by mass of at least one reinforcing filler selected from the group consisting of silica-based inorganic fillers, metal oxides, metal hydroxides, and carbon black, based on 100 parts by mass of the conjugated diene copolymer.

[0139] As the silica-based inorganic filler contained in the conjugated diene copolymer composition, it is preferable to use solid particles whose main constituent unit is SiO2 or silicate. Here, the main component means a component that occupies 50% by mass or more of the total, preferably a component that occupies 70% by mass or more, and more preferably a component that occupies 90% by mass or more.

[0140] Specific examples of silica-based inorganic fillers include inorganic fibrous materials such as silica, clay, talc, mica, diatomaceous earth, wollastonite, montmorillonite, zeolite, and glass fiber. The silica-based inorganic fillers may be used alone or in combination of two or more. In addition, silica-based inorganic fillers with hydrophobic surfaces and mixtures of silica-based inorganic fillers and inorganic fillers other than silica-based inorganic fillers may also be used. Among these, silica and glass fiber are preferred, and silica is more preferred.

[0141] As the silica, dry silica, wet silica, synthetic silicate silica, etc. can be used. Among them, wet silica is preferred because it is superior in both improving the fracture properties and wet skid resistance performance.

[0142] From the viewpoint of obtaining good abrasion resistance and fracture characteristics, the nitrogen adsorption specific surface area required by the BET adsorption method for silica-based inorganic fillers is 170 to 300 m 2 / g, and 200 to 300m 2 It is more preferable that the molecular weight is / g.

[0143] The amount of silica-based inorganic filler in the conjugated diene copolymer composition is preferably 0.5 to 200 parts by mass relative to 100 parts by mass of the conjugated diene copolymer. The upper limit of the amount of silica-based inorganic filler relative to 100 parts by mass of the conjugated diene copolymer, which is the rubber component, is preferably 100 parts by mass or less, more preferably 75 parts by mass or less. The lower limit is preferably 5 parts by mass or more, more preferably 20 parts by mass or more, and particularly preferably 35 parts by mass or more. When the amount of silica-based inorganic filler is within the above range, the effect of adding the filler is exhibited, and the dispersibility of the silica-based inorganic filler is improved, and the processability of the obtained composition is improved and the mechanical strength is improved.

[0144] To the conjugated diene copolymer composition, carbon black may be added as a reinforcing filler other than the silica-based inorganic filler.

[0145] As the carbon black, for example, carbon black of each class such as SRF, FEF, HAF, ISAF, SAF, etc. can be used. From the viewpoint of excellent reinforcing effect, carbon black having a nitrogen adsorption specific surface area of ​​50 m 2 / g or more, and a DBP (dibutyl phthalate) oil absorption of 80 mL / 100 g of carbon black is preferred.

[0146] The amount of carbon black to be added is 0.5 to 200 parts by mass, preferably 3 to 100 parts by mass, and more preferably 5 to 50 parts by mass, based on 100 parts by mass of the conjugated diene copolymer.

[0147] In addition to the silica-based inorganic filler and carbon black, a metal oxide or metal hydroxide may be added as a reinforcing filler to the conjugated diene copolymer composition. The metal oxide is preferably a solid particle having a main component represented by the chemical formula MxOy (M represents a metal atom, and x and y each represent an integer of 1 to 6). Here, the main component means a component that accounts for 50% by mass or more of the total, preferably a component that accounts for 70% by mass or more, and more preferably a component that accounts for 90% by mass or more.

[0148] Examples of the metal oxide include alumina, titanium oxide, magnesium oxide, and zinc oxide. Examples of the metal hydroxide include aluminum hydroxide, magnesium hydroxide, and zirconium hydroxide. The metal oxides and metal hydroxides may be used alone or in combination of two or more. In addition, mixtures with inorganic fillers other than the metal oxides and metal hydroxides may also be used.

[0149] The conjugated diene copolymer composition may contain a silane coupling agent. The silane coupling agent has a function of strengthening the interaction between the conjugated diene copolymer and the silica-based inorganic filler, and has a group having affinity or binding properties for each of them.

[0150] Specific examples of the silane coupling agent include bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide, and bis-[2-(triethoxysilyl)-ethyl]-tetrasulfide.

[0151] The amount of the silane coupling agent is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 20 parts by mass, and even more preferably 1 to 15 parts by mass, relative to 100 parts by mass of the silica-based inorganic filler. By setting the amount of the silane coupling agent in the above range, a sufficient blending effect can be obtained and economic efficiency can be improved.

[0152] The above-mentioned conjugated diene copolymer composition can be produced by mixing the above-mentioned components.

[0153] The method of mixing the conjugated diene copolymer with at least one reinforcing filler selected from the group consisting of silica-based inorganic fillers, metal oxides, metal hydroxides, and carbon black, and optionally with a silane coupling agent, is not particularly limited. For example, a melt-kneading method using a general mixer such as an open roll, a Banbury mixer, a kneader, a single-screw extruder, a twin-screw extruder, or a multi-screw extruder, and a method of dissolving and mixing each component and then removing the solvent by heating, etc., can be mentioned. Among these, the melt-kneading method using a roll, a Banbury mixer, a kneader, or an extruder is preferred from the viewpoint of productivity and good kneading. In addition, either a method of kneading the rubber component and various compounding agents at once or a method of mixing them in several batches can be applied.

[0154] In the present invention, the degree of polymer concentration on the filler surface can be expressed by the bound rubber amount of the modified conjugated diene polymer at 25° C. From the viewpoint of improving abrasion resistance and breaking strength, the bound rubber amount in the conjugated diene copolymer composition (rubber composition) after the above-mentioned kneading is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more. The amount of bound rubber can be measured by the method described in the Examples below.

[0155] The conjugated diene copolymer composition may be a vulcanized composition that has been vulcanized with a vulcanizing agent. Examples of the vulcanizing agent that can be used include radical generators such as organic peroxides and azo compounds, oxime compounds, nitroso compounds, polyamine compounds, sulfur, and sulfur compounds. Examples of the sulfur compounds include sulfur monochloride, sulfur dichloride, disulfide compounds, and polymeric polysulfur compounds.

[0156] The amount of the vulcanizing agent used is not particularly limited, but is preferably 0.01 to 20 parts by mass, and more preferably 0.1 to 15 parts by mass, relative to 100 parts by mass of the conjugated diene copolymer. As the vulcanization method, a conventionally known method can be applied, and the vulcanization temperature is, for example, preferably 120°C to 200°C, and more preferably 140°C to 180°C.

[0157] In vulcanization, a vulcanization accelerator may be used as necessary. As the vulcanization accelerator, a conventionally known material may be used, and examples thereof include sulfenamide-based, guanidine-based, thiuram-based, aldehyde-amine-based, aldehyde-ammonia-based, thiazole-based, thiourea-based, and dithiocarbamate-based vulcanization accelerators. As the vulcanization aid, zinc oxide, stearic acid, etc. may be used.

[0158] The amount of the vulcanization accelerator used is not particularly limited, but is preferably 0.01 to 20 parts by mass, and more preferably 0.1 to 15 parts by mass, based on 100 parts by mass of the conjugated diene copolymer.

[0159] In order to improve processability, the conjugated diene copolymer composition of the present invention may be blended with a rubber softener. Suitable rubber softeners include mineral oils, liquids, and low molecular weight synthetic softeners.

[0160] Mineral oil-based rubber softeners, called process oils or extender oils, which are used to soften rubber, increase its volume, and improve its processability, are mixtures of aromatic rings, naphthenic rings, and paraffin chains, and those in which the carbon number of the paraffin chain is 50% or more of the total carbon are called paraffinic, those in which the carbon number of the naphthenic ring is 30 to 45% are called naphthenic, and those in which the aromatic carbon number is more than 30% are called aromatic. The rubber softener used in this embodiment is preferably naphthenic and / or paraffinic.

[0161] The amount of the rubber softener to be added is not particularly limited, but is preferably 10 to 80 parts by mass, and more preferably 20 to 50 parts by mass, per 100 parts by mass of the conjugated diene copolymer.

[0162] The conjugated diene copolymer composition may contain various additives such as softeners and fillers other than those described above, as well as heat stabilizers, antistatic agents, weather stabilizers, antioxidants, colorants, lubricants, etc., within the scope of the present embodiment. Specific examples of fillers include calcium carbonate, magnesium carbonate, aluminum sulfate, barium sulfate, etc. Softeners that are blended as necessary to adjust the hardness and fluidity of the target product include, for example, liquid paraffin, castor oil, linseed oil, etc. Known materials can be used as heat stabilizers, antistatic agents, weather stabilizers, antioxidants, colorants, and lubricants.

[0163] The cross-linked rubber product of the present invention can be obtained by subjecting the above-mentioned rubber composition to a cross-linking treatment. For example, the above-mentioned rubber composition is extruded and molded according to the shape of the tire (specifically, the shape of the tread), and the tread is produced by heating and pressurizing the extrusion in a vulcanizer, and the tread is assembled with other components to produce the desired tire.

[0164] The conjugated diene copolymer composition (rubber composition) of the present invention has excellent mechanical strength and abrasion resistance when it is made into the above-mentioned rubber cross-linked product. Therefore, as described above, it can be suitably applied to tire components such as treads and sidewall components of tires such as fuel-efficient tires, large tires, and high-performance tires. In addition to the tire components, it can also be suitably used for rubber belts, rubber hoses, footwear materials, etc. EXAMPLES

[0165] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In each example, all parts are by weight unless otherwise specified, and each physical property was evaluated by the following method.

[0166] 1) Molecular weight and molecular weight distribution The molecular weight and molecular weight distribution were measured using GPC (Tosoh Corporation, HLC-8220GPC) with tetrahydrofuran (THF) as the solvent, a flow rate of 1.0 ml / min, a column temperature of 38° C., and a calibration curve based on monodisperse polystyrene.

[0167] 2) Structure of polyfunctional vinyl aromatic copolymer Using a JEOL JNM-LA600 nuclear magnetic resonance spectrometer, 13 C-NMR and 1 The NMR analysis was performed using 1H NMR spectroscopy. Chloroform-d1 was used as the solvent, and the resonance line of tetramethylsilane was used as the internal standard.

[0168] 3) Mooney viscosity (ML(1+4)100℃) According to JIS K6300-1, the measurements were performed using an L-shaped rotor, 1 minute preheating, 4 minutes rotor operation time, and a temperature of 100°C.

[0169] 4) Confirmation of microgelation (Haze) A sample obtained by dissolving 0.5 g of copolymer rubber in 100 g of toluene was placed in a quartz cell, and its haze (turbidity) was measured using an integrating sphere type light transmittance measuring device (Nippon Denshoku Industries, SZ-Σ90) with toluene as the reference sample. When the haze value was less than 0.5, it was evaluated as ◯ (no microgels were present), and when the haze value exceeded 0.5, it was evaluated as × (the microgels were present).

[0170] 5) Glass transition temperature (Tg) A solution of polyfunctional vinyl aromatic copolymer dissolved in toluene was uniformly applied to a glass substrate so that the thickness after drying was 20 μm, and the substrate was heated for 30 minutes at 90°C using a hot plate and dried. The resin film obtained together with the glass substrate was set in a TMA (thermomechanical analyzer), heated to 220°C at a heating rate of 10°C / min under a nitrogen stream, and further heated at 220°C for 20 minutes to remove the remaining solvent and harden the polyfunctional vinyl aromatic copolymer. After the glass substrate was allowed to cool to room temperature, an analytical probe was brought into contact with the sample in the TMA measuring device, and a scan measurement was performed from 30°C to 360°C at a heating rate of 10°C / min under a nitrogen stream, and the softening temperature was determined by the tangential method.

[0171] 6) Vinyl bond content of conjugated diene units The sample was made into a carbon disulfide solution, and the infrared spectrum was measured in the range of 600-1000 cm-1 using a solution cell, and the vinyl bond amount was calculated according to the Hampton (styrene-butadiene copolymer) method formula from the absorbance at a specified wave number. The device used was a Spectrum 100 made by PerkinElmer.

[0172] 7) Bound rubber content (%) A mixture of 100 parts by mass of modified conjugated diene polymer and wet silica (BET specific surface area: 205±10 m 2 Using an enclosed mixer with a mixing chamber volume of 2 liters, 60 parts by mass of rubber composition (trade name "Nipsil AQ") and 60 parts by mass of rubber composition (trade name "Nipsil AQ" manufactured by Tosoh Silica Co., Ltd.) are mixed at a ratio of 60% {(volume of rubber composition being mixed / volume of mixing chamber) x 100}, and when the maximum mixing temperature of 160°C is reached, the rubber mixture is discharged to obtain rubber composition M for measuring the amount of bound rubber. 0.2 g of this rubber composition M was cut into 1 mm squares and the mass was measured, then added to 25 mL of toluene and left at 25°C for 48 hours. Then, it was filtered through an ADVANTEC glass fiber filter to separate the toluene insolubles, which were then vacuum dried at 25°C and weighed to determine the amount of bound rubber using the following formula. Bound rubber amount (%)={(mass of toluene insoluble matter−mass of wet silica in rubber composition M) / (mass of rubber composition M−mass of wet silica in rubber composition M)}×100 The BET specific surface area of ​​silica is measured in accordance with ISO5794 / 1.

[0173] 8) Tensile strength The 300% modulus was measured according to the tensile test method of JIS K6251. In the first invention, the measured value of the crosslinked rubber obtained in Comparative Example 1 was set as 100 and indexed. In the second invention, the measured value of the crosslinked rubber obtained in Example 20B was set as 100 and the values ​​were indexed. In the third invention, the measured value of the crosslinked rubber obtained in Example 10C was set as 100 and indexed. A larger index value indicates better tensile strength.

[0174] 9) Abrasion resistance The amount of wear at a slip rate of 30% was measured using a method using a Lambourn type abrasion tester conforming to JIS K6264. In the first invention, the measured value of the crosslinked rubber obtained in Comparative Example 1 was set as 100 and indexed. In the second invention, the measured value of the crosslinked rubber obtained in Example 20 was set as 100 and the results were indexed. In the third invention, the measured value of the crosslinked rubber obtained in Example 10 was set as 100 and indexed. The higher the index value, the better the abrasion resistance.

[0175] 10) Solvent soluble The copolymer was soluble in toluene, xylene, THF, dichloroethane, dichloromethane, and chloroform. When 100 g or more of the copolymer dissolved in 100 g of each of the above solvents and no gel formation was observed, the copolymer was rated as having solvent solubility of ◯.

[0176] The raw materials or their abbreviations used in the examples are as follows. DVB-630; a mixture of divinylbenzene and ethylvinylbenzene components; divinylbenzene content 63.0 wt%, manufactured by Nippon Steel Chemical & Materials Co., Ltd. Indene; Wako Pure Chemical Industries, Ltd. BHT; 2,6-di-tert-butyl-p-cresol BTESPA; Bis(3-trimethoxysilylpropyl)methylamine

[0177] <First embodiment of the present invention> Example 1A 92.98g of DVB-630 (0.45 mol of divinylbenzene component, 0.26 mol of ethylvinylbenzene component), 276.58g (2.29 mol) of indene, and 1.50 mol (172.5mL) of n-propyl acetate were charged into a 1.0L reactor, and 60 mmol of boron trifluoride diethyl ether complex (7.5mL) was added at 70°C, and the reaction was carried out for 2.5 hours. After the polymerization solution was stopped with an aqueous sodium hydrogen carbonate solution, the oil layer was washed three times with pure water, and the copolymer was recovered by degassing under reduced pressure at 60°C. The obtained copolymer was weighed, and it was confirmed that 221.7g of copolymer 1A was obtained. In the examples and comparative examples, the copolymers obtained are soluble polyfunctional vinyl aromatic copolymers.

[0178] The obtained polyfunctional vinyl aromatic copolymer 1A had an Mn of 828, an Mw of 2620, and an Mw / Mn of 3.17. 13C-NMR and 1H-NMR analyses revealed that the polyfunctional vinyl aromatic copolymer A contained 13.8 mol% (15.1 wt%) of structural units derived from divinylbenzene, a total of 7.9 mol% (8.8 wt%) of structural units derived from ethylvinylbenzene, and 78.2 mol% (76.1 wt%) of structural units derived from indene. The polyfunctional vinyl aromatic copolymer 1A contained 11.0 mol% (12.1 wt%) of structural units derived from divinylbenzene having residual vinyl groups (corresponding to structural unit (a1)). Furthermore, the TMA measurement of the cured product showed that the Tg was 182° C. and the softening temperature was over 280° C. The TGA measurement showed that the weight loss at 350° C. was 1.52 wt%. On the other hand, the compatibility with epoxy resin was good. The polyfunctional vinyl aromatic copolymer 1A was soluble in solvents.

[0179] Example 2A 187.11g of DVB-630 (0.90 mol of divinylbenzene component, 0.53 mol of ethylvinylbenzene component), 182.37g (1.57 mol) of indene, and 1.50 mol (172.5mL) of n-propyl acetate were charged into a 1.0L reactor, and 40 mmol of boron trifluoride diethyl ether complex (5.0mL) was added at 70°C and reacted for 3.5 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, devolatilized under reduced pressure at 60°C, and the polyfunctional vinyl aromatic copolymer was recovered by reprecipitation, filtration, and drying under strong stirring using 4,500mL of methanol. The obtained polyfunctional vinyl aromatic copolymer was weighed, and it was confirmed that 238.7g of polyfunctional vinyl aromatic copolymer 2A was obtained.

[0180] The obtained polyfunctional vinyl aromatic copolymer 2A had an Mn of 1240, an Mw of 3580, and an Mw / Mn of 2.89. Copolymer 2A contained 29.6 mol% (31.3 wt%) of structural units derived from divinylbenzene, a total of 17.9 mol% (19.2 wt%) of structural units derived from ethylvinylbenzene, and 52.5 mol% (49.5 wt%) of structural units derived from indene. The content of structural units derived from divinylbenzene having residual vinyl groups contained in polyfunctional vinyl aromatic copolymer 2A was 19.5 mol% (20.6 wt%). The cured product had a Tg of 205° C. and a softening temperature of over 280° C. The TGA measurement showed that the weight loss at 350° C. was 0.96 wt%. On the other hand, the compatibility with epoxy resin was rated as good. The polyfunctional vinyl aromatic copolymer 2A was soluble in solvents.

[0181] Example 3A 31.16g of DVB-630 (0.15 mol of divinylbenzene component, 0.09 mol of ethylvinylbenzene component), 320.83g (2.76 mol) of indene, and 1.50 mol (172.5mL) of n-propyl acetate were charged into a 1.0L reactor, and 80 mmol of boron trifluoride diethyl ether complex (10.0mL) was added at 70°C and reacted for 3.0 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, devolatilized under reduced pressure at 60°C, and the polyfunctional vinyl aromatic copolymer was recovered by reprecipitation, filtration, and drying under strong stirring using 4,500mL of methanol. The obtained polyfunctional vinyl aromatic copolymer was weighed, and it was confirmed that 256.3g of polyfunctional vinyl aromatic copolymer 3A was obtained.

[0182] The obtained polyfunctional vinyl aromatic copolymer 3A had an Mn of 659, an Mw of 2560, and an Mw / Mn of 3.88. Copolymer 3A contained 5.1 mol % (5.8 wt %) of structural units derived from divinylbenzene, a total of 2.9 mol % (3.3 wt %) of structural units derived from ethylvinylbenzene, and 92.0 mol % (90.9 wt %) of structural units derived from indene. The content of structural units derived from divinylbenzene having residual vinyl groups contained in polyfunctional vinyl aromatic copolymer 3A was 3.3 mol % (3.8 wt %). The cured product had a Tg of 192° C. and a softening temperature of over 280° C. The TGA measurement showed that the weight loss at 350° C. was 1.63 wt%. On the other hand, the compatibility with epoxy resin was rated as good. The polyfunctional vinyl aromatic copolymer 3A was soluble in solvents.

[0183] Comparative Example 1A 249.41g of DVB-630 (1.20 mol of divinylbenzene component, 0.70 mol of ethylvinylbenzene component), 127.20g (1.10 mol) of indene, and 1.50 mol (172.5mL) of n-propyl acetate were charged into a 1.0L reactor, and 40 mmol of boron trifluoride diethyl ether complex (5.0mL) was added at 70°C and reacted for 3.0 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, devolatilized under reduced pressure at 60°C, and the polyfunctional vinyl aromatic copolymer was recovered by reprecipitation, filtration, and drying under strong stirring using 4,500mL of methanol. The obtained polyfunctional vinyl aromatic copolymer was weighed, and it was confirmed that 253.6g of polyfunctional vinyl aromatic copolymer C1A was obtained.

[0184] The obtained polyfunctional vinyl aromatic copolymer C1A had an Mn of 1430, an Mw of 5030, and an Mw / Mn of 3.52. The copolymer C1A contained 40.2 mol% (41.6 wt%) of structural units derived from divinylbenzene, a total of 23.6 mol% (25.0 wt%) of structural units derived from ethylvinylbenzene, and 36.2 mol% (33.4 wt%) of structural units derived from indene. The content of structural units derived from divinylbenzene having residual vinyl groups contained in the polyfunctional vinyl aromatic copolymer C1A was 26.5 mol% (27.4 wt%). The cured product had a Tg of 168° C. and a softening temperature of over 280° C. The TGA measurement showed that the weight loss at 350° C. was 2.13 wt%. On the other hand, the compatibility with epoxy resin was rated as good. The polyfunctional vinyl aromatic copolymer C1A was soluble in solvents.

[0185] Comparative example 2A 12.46g of DVB-630 (0.06 mol of divinylbenzene component, 0.04 mol of ethylvinylbenzene component), 337.44g (2.90 mol) of indene, and 1.50 mol (172.5 mL) of n-propyl acetate were charged into a 1.0L reactor, and 80 mmol of boron trifluoride diethyl ether complex (10.0 mL) was added at 70 ° C. and reacted for 4.5 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, devolatilized under reduced pressure at 60 ° C., and the polyfunctional vinyl aromatic copolymer was recovered by reprecipitation, filtration, and drying under strong stirring using 4,500 mL of methanol. The obtained polyfunctional vinyl aromatic copolymer was weighed, and it was confirmed that 212.6 g of polyfunctional vinyl aromatic copolymer C2A was obtained.

[0186] The obtained polyfunctional vinyl aromatic copolymer C2A had an Mn of 596, an Mw of 1750, and an Mw / Mn of 2.93. The copolymer C2A contained 1.96 mol% (2.19 wt%) of structural units derived from divinylbenzene, a total of 1.16 mol% (1.32 wt%) of structural units derived from ethylvinylbenzene, and 96.88 mol% (96.49 wt%) of structural units derived from indene. The content of structural units derived from divinylbenzene having residual vinyl groups contained in the polyfunctional vinyl aromatic copolymer C2A was 1.30 mol% (1.45 wt%). Furthermore, TMA measurement of the cured product showed that the Tg was 178° C. and the softening temperature was 201° C. TGA measurement showed that the weight loss at 350° C. was 2.45 wt%. On the other hand, compatibility with epoxy resins was rated as good. The polyfunctional vinyl aromatic copolymer C2A was soluble in solvents.

[0187] Comparative example 3A 320.5mL of DVB-810 (1.82 mol of divinylbenzene component, 0.43 mol of ethylvinylbenzene component), 0.28 mol (36.9mL) of n-butyl acetate, and 140mL of toluene were charged into a 1.0L reactor, and a solution of 40 mmol of methanesulfonic acid dissolved in 0.12 mol (15.7mL) of n-butyl acetate was added at 70°C, and the reaction was carried out for 6 hours. After the polymerization solution was stopped with calcium hydroxide, filtration was carried out using activated alumina as a filter aid. Then, the mixture was devolatilized under reduced pressure at 60°C to obtain 22.6g of polyfunctional vinyl aromatic copolymer C3A. The obtained polyfunctional vinyl aromatic copolymer C3A had an Mn of 1085, an Mw of 12400, and an Mw / Mn of 11.4. The polyfunctional vinyl aromatic copolymer F contained 84.0 mol% (83.8 wt%) of structural units derived from divinylbenzene and a total of 16.0 mol% (16.2 wt%) of structural units derived from ethylvinylbenzene. The content of structural units derived from divinylbenzene having residual vinyl groups contained in the polyfunctional vinyl aromatic copolymer C3A was 53.8 mol% (53.6 wt%). The cured product had a Tg of 82° C. and a softening temperature of 93° C. The TGA measurement showed that the weight loss at 350° C. was 8.25 wt%. On the other hand, the compatibility with epoxy resin was rated as good. The multifunctional vinyl aromatic copolymer C3A was soluble in solvents.

[0188] Example 4A Into a nitrogen-purged autoclave reactor having an internal volume of 0.5 liters, 245 g of cyclohexane, 2.5 g of THF, 10 g of styrene, 40 g of 1,3-butadiene, and 0.10 g of the copolymer 1A obtained in Example 1A were added. At 25°C, 5 g of a cyclohexane solution containing 50 mg of sec-butyllithium was added to initiate polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and reached a maximum temperature of 85°C. After confirming that the polymerization conversion rate reached 99%, 50 mg of isopropanol was added to terminate the polymerization, and 2,6-di-tert-butyl-p-cresol (BHT) was added to the reaction solution. The solvent was then removed by steam stripping to obtain conjugated diene copolymer 4A. The physical properties of the obtained conjugated diene copolymer 4A are shown in Table 1A.

[0189] Example 5A 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.10g of the copolymer 1A obtained in Example 1A was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane, and no gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 85°C. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Then, the solvent was removed by steam stripping to obtain a conjugated diene copolymer 5A. The physical properties of the obtained conjugated diene copolymer 5A are shown in Table 1A.

[0190] Example 6A 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.050g of copolymer 2A obtained in Example 2 was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane, and no gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the polymerization heat, and the maximum temperature reached 83°C. After the polymerization reaction was completed, 21mmol of BTESPA was added as a modifier to the reactor to carry out a modification reaction. The modification reaction was carried out for 5 minutes at a temperature condition of 80°C to obtain a polymer solution. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Then, the solvent was removed by steam stripping to obtain a conjugated diene copolymer 6A. The physical properties of the obtained conjugated diene copolymer 6A are shown in Table 1A.

[0191] Example 7A 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.30g of copolymer 3A obtained in Example 3A was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane, and no gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the polymerization heat, and the maximum temperature reached 81°C. After the polymerization reaction was completed, 21mmol of BTESPA was added as a modifier to the reactor to carry out a modification reaction. The modification reaction was carried out for 5 minutes at a temperature condition of 80°C to obtain a polymer solution. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Then, the solvent was removed by steam stripping to obtain a conjugated diene copolymer 7A. The physical properties of the obtained conjugated diene copolymer 7A are shown in Table 1A.

[0192] Comparative example 4A 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.0375g of the copolymer C1A obtained in Comparative Example 1A was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was mostly soluble in cyclohexane, but the generation of gel was observed visually. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 82°C. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. The solvent was then removed by steam stripping to obtain a conjugated diene copolymer C4A. The physical properties of the obtained conjugated diene copolymer C4A are shown in Table 1A.

[0193] Comparative example 5A 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.75g of the copolymer C2A obtained in Comparative Example 2A was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane, and no gel formation was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 78°C. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Then, the solvent was removed by steam stripping to obtain a conjugated diene copolymer C5A. The physical properties of the obtained conjugated diene copolymer C5A are shown in Table 1A.

[0194] Comparative Example 6A 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.020g of the copolymer C3A obtained in Comparative Example 3A was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was partially soluble in cyclohexane, and the generation of gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 83°C. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. The solvent was then removed by steam stripping to obtain a conjugated diene copolymer C6A. The physical properties of the obtained conjugated diene copolymer C6A are shown in Table 1A. In Table 1A, the diene copolymer means a conjugated diene copolymer, and the same applies to the other tables.

[0195] [Table 1A]

[0196] Example 8A Conjugated diene copolymer 4A, process oil, carbon black, zinc oxide, stearic acid and an antioxidant were kneaded at 155° C. and 60 rpm for 4 minutes using a Labo Plastomill. To the kneaded product obtained by the above kneading, sulfur and a vulcanization accelerator were added, and the mixture was kneaded at 70° C. and 60 rpm for 1 minute using a Labo Plastomill, and then vulcanized to obtain a crosslinked rubber 8A. The mixing ratio of each additive is shown in Table 2A, and the physical properties of crosslinked rubber 8A are shown in Table 3A.

[0197] Examples 9A to 11A, Comparative Examples 7A to 9A Crosslinked rubbers 9A to 11A, C7A to C9A were obtained in the same manner as in Example 8A, except that the conjugated diene copolymers 5A, 6A, 7A, C4A, C5A, and C6A synthesized in the above examples or comparative examples were used instead of the conjugated diene copolymer 4A. The type of conjugated diene copolymer used and the physical properties of the resulting crosslinked rubbers 9A to 11A and C7A to C9A are shown in Table 3A.

[0198] [Table 2A]

[0199] In Table 2A, the additives used are as follows: Process oil: Idemitsu Kosan Dyna Process Oil AC-12 Sulfur: Powdered sulfur manufactured by Tsurumi Chemical Industry Co., Ltd. Zinc oxide: Zinc oxide No. 1 manufactured by Mitsui Mining & Smelting Stearic acid: NOF Corporation Silica: Degussa, ULTRASIL VN3 Carbon black: Nitelon #300 made by Nippon Steel Carbon Accelerator: N-tert-butylbenzothiazole-2-sulfenamide Anti-aging agent: Noccela NS manufactured by Ouchi Shinko Chemical Industry

[0200] [Table 3A]

[0201] In Table 3A, the tensile strength index and the abrasion resistance index are calculated assuming that the value of the crosslinked rubber of Comparative Example 7A is 100. From Table 3A, it can be seen that the crosslinked rubber of the present invention using the polyfunctional vinyl aromatic copolymer of the present invention provides equal to or better processability than the case using divinylbenzene, a known branching agent, and is excellent in tensile strength and abrasion resistance in vulcanized rubber blended with carbon black.

[0202] <Second embodiment of the present invention> Example 1B 9.30g of DVB-630 (0.045 mol of divinylbenzene component, 0.026 mol of ethylvinylbenzene component), 148.79g (1.43 mol) of styrene, and 1.50 mol (172.5mL) of n-propyl acetate were charged into a 1.0L reactor, and 200 mmol of boron trifluoride diethyl ether complex (25.1mL) was added at 50°C and reacted for 2.5 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, and the copolymer was removed under reduced pressure at 60°C to recover 90.1g of polyfunctional vinyl aromatic copolymer 1B.

[0203] The resulting polyfunctional vinyl aromatic copolymer 1B had an Mn of 4140, an Mw of 9550, and an Mw / Mn of 2.31.13 C-NMR and 1 By carrying out H-NMR analysis, the polyfunctional vinyl aromatic copolymer A contained 3.0 mol% (3.7 wt%) of structural units derived from divinylbenzene, 1.4 mol% (1.8 wt%) of structural units derived from ethylvinylbenzene, and 95.5 mol% (94.5 wt%) of structural units derived from styrene. The crosslinked structural units (a2) derived from the divinyl aromatic compound represented by the formula (2) were 0.24 mol% (0.30 wt%), so the degree of crosslinking was 0.08. In addition, the structural units (a1) derived from divinylbenzene having residual vinyl groups contained in the polyfunctional vinyl aromatic copolymer 1B were 2.76 mol% (3.40 wt%), so the molar fraction of the vinyl group-containing structural units (a1) relative to the sum of the structural units (a) and (b) was 0.028. Furthermore, TMA measurement of the cured product showed that it had a Tg of 105°C and a softening temperature of 128°C. The TGA measurement results showed that the weight loss at 350° C. was 1.36 wt%. A sample prepared by dissolving 0.5 g of polyfunctional vinyl aromatic copolymer 1B in 100 g of toluene was placed in a quartz cell, and the haze (turbidity) was measured using an integrating sphere light transmittance measuring device with toluene as the reference sample. The haze value was 0.00.

[0204] Example 2B 18.60g of DVB-630 (0.090 mol of divinylbenzene component, 0.053 mol of ethylvinylbenzene component), 141.34g (1.36 mol) of styrene, and 1.00 mol (115.0mL) of n-propyl acetate were charged into a 1.0L reactor, and 50 mmol of boron trifluoride diethyl ether complex (6.1mL) was added at 60°C, and the reaction was carried out for 3.0 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, and the copolymer was removed under reduced pressure at 60°C, and 95.8g of polyfunctional vinyl aromatic copolymer 2B was obtained.

[0205] The polyfunctional vinyl aromatic copolymer 2B had an Mn of 2620, an Mw of 11800, and an Mw / Mn of 4.51, and contained 7.37 mol% (8.97 wt%) of structural units derived from divinylbenzene, 3.34 mol% (4.12 wt%) of structural units derived from ethylvinylbenzene, and 89.3 mol% (86.9 wt%) of structural units derived from styrene. The crosslinked structural units (a2) were 1.55 mol% (1.82 wt%), the degree of crosslinking was 0.21, the vinyl group-containing structural units (a1) were 5.82 mol% (7.15 wt%), and the molar fraction of the structural units (a1) was 0.058. The cured product had a Tg of 158° C. and a softening temperature of 265° C. The weight loss at 350° C. was 1.28 wt %. The haze value of the polyfunctional vinyl aromatic copolymer 2B was 0.01.

[0206] Example 3B 31.00g of DVB-630 (0.150 mol of divinylbenzene component, 0.088 mol of ethylvinylbenzene component), 131.43g (1.262 mol) of styrene, and 1.50 mol (172.5mL) of n-propyl acetate were charged into a 1.0L reactor, and 60 mmol of boron trifluoride diethyl ether complex (7.5mL) was added at 55°C and reacted for 5.0 hours. After the polymerization solution was stopped with an aqueous sodium hydrogen carbonate solution, the oil layer was washed three times with pure water, and the copolymer was recovered by degassing at 60°C, and 96.3g of polyfunctional vinyl aromatic copolymer 3B was obtained.

[0207] The polyfunctional vinyl aromatic copolymer 3B had an Mn of 2950, ​​an Mw of 13400, and an Mw / Mn of 4.54. It contained 11.63 mol% (13.91 wt%) of structural units derived from divinylbenzene, a total of 5.87 mol% (7.13 wt%) of structural units derived from ethylvinylbenzene, and 82.50 mol% (78.96 wt%) of structural units derived from styrene. The crosslinked structural units (a2) were 3.14 mol% (3.76 wt%), and the degree of crosslinking was 0.27. The structural units (a1) were 8.49 mol% (10.16 wt%), and the molar fraction of the vinyl group-containing structural units (a1) was 0.085. The cured product had a Tg of 165°C, a softening temperature of 280°C or higher, and a weight loss of 1.46 wt% at 350°C. The haze value of the polyfunctional vinyl aromatic copolymer 3B was 0.04.

[0208] Example 4B 46.49g of DVB-630 (0.225 mol of divinylbenzene component, 0.132 mol of ethylvinylbenzene component), 119.03g (1.143 mol) of styrene, and 1.50 mol (172.5mL) of n-propyl acetate were charged into a 1.0L reactor, and 60 mmol of boron trifluoride diethyl ether complex (7.54mL) was added at 50°C, and the reaction was carried out for 3.5 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, and the copolymer was recovered by degassing at 60°C, and 96.10g of polyfunctional vinyl aromatic copolymer 4B was obtained.

[0209] The polyfunctional vinyl aromatic copolymer 4B had an Mn of 3870, an Mw of 23600, and an Mw / Mn of 6.10. It contained 20.64 mol% (23.98 wt%) of structural units derived from divinylbenzene, 9.09 mol% (10.72 wt%) of structural units derived from ethylvinylbenzene, and 70.27 mol% (65.30 wt%) of structural units derived from styrene. The crosslinked structural units (a2) were 6.61 mol% (7.67 wt%), the degree of crosslinking was 0.32, the vinyl group-containing structural units (a1) were 14.04 mol% (16.31 wt%), and the molar fraction of the vinyl group-containing structural units (a1) was 0.140. The cured product had a Tg of 178°C, a softening temperature of 280°C or higher, and a weight loss at 350°C of 1.53wt%. The haze value of the polyfunctional vinyl aromatic copolymer 4B was 0.07.

[0210] Example 5B 77.49g of DVB-630 (0.375 mol of divinylbenzene component, 0.220 mol of ethylvinylbenzene component), 94.23g (0.905 mol) of styrene, and 1.57 mol (180.2mL) of n-propyl acetate were charged into a 1.0L reactor, and 23.3 mmol of boron trifluoride diethyl ether complex (2.93mL) was added at 50°C, and the reaction was carried out for 5.25 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, and the copolymer was recovered by degassing at 60°C, and 76.19g of polyfunctional vinyl aromatic copolymer 5B was obtained.

[0211] The polyfunctional vinyl aromatic copolymer 5B had an Mn of 4230, an Mw of 26200, and an Mw / Mn of 6.19. It contained 39.29 mol % (43.12 wt %) of structural units derived from divinylbenzene, 15.08 mol % (16.81 wt %) of structural units derived from ethylvinylbenzene, and 45.63 mol % (40.07 wt %) of structural units derived from styrene. The crosslinked structural unit (a2) was 16.89 mol % (18.54 wt %) with a crosslinking degree of 0.43, the vinyl group-containing structural unit (a1) was 22.39 mol % (24.58 wt %) with a molar fraction of the structural unit (a1) being 0.224. The cured product had no Tg, a softening temperature of 280°C or higher, and a weight loss of 1.61 wt% at 350°C. The haze value of the polyfunctional vinyl aromatic copolymer 5B was 0.09.

[0212] Comparative example 1B 320.5mL of DVB-810 (1.82 mol of divinylbenzene component, 0.43 mol of ethylvinylbenzene component), 0.28 mol (36.9mL) of n-butyl acetate, and 140mL of toluene were charged into a 1.0L reactor, and a solution of 40 mmol of methanesulfonic acid dissolved in 0.12 mol (15.7mL) of n-butyl acetate was added at 70°C, and the reaction was carried out for 6 hours. After the polymerization solution was stopped with calcium hydroxide, filtration was carried out using activated alumina as a filter aid. Then, the mixture was devolatilized under reduced pressure at 60°C to obtain 22.6g of polyfunctional vinyl aromatic copolymer C1B. The polyfunctional vinyl aromatic copolymer C1B had an Mn of 1085, an Mw of 12400, and an Mw / Mn of 11.4, and contained 84.0 mol % (83.8 wt %) of structural units derived from divinylbenzene and a total of 16.0 mol % (16.2 wt %) of structural units derived from ethylvinylbenzene. The crosslinked structural units (a2) were 2.60 mol % (2.59 wt %), the degree of crosslinking was 0.031, the vinyl group-containing structural units (a1) were 11.40 mol % (11.37 wt %), and the molar fraction of the vinyl group-containing structural units (a1) was 0.114. The cured product had a Tg of 82° C., a softening temperature of 93° C., and a weight loss of 8.25 wt% at 350° C. On the other hand, compatibility with epoxy resins was rated as good. The haze value of the polyfunctional vinyl aromatic copolymer C1B was 0.02.

[0213] Comparative Example 2B 1.5 mol (195.3 g) of divinylbenzene, 0.88 mol (114.7 g) of ethylvinylbenzene, 12.6 mol (1314.3 g) of styrene, and 15.0 mol (1532.0 g) of n-propyl acetate were charged into a 5.0 L reactor, and 600 mmol of boron trifluoride diethyl ether complex was added at 70 ° C. and reacted for 4 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, and the copolymer was recovered by degassing under reduced pressure at 60 ° C. The obtained copolymer was weighed, and it was confirmed that 820.8 g of copolymer C2B was obtained.

[0214] Copolymer C2B had an Mn of 1490, an Mw of 12600, and an Mw / Mn of 8.44. Copolymer G contained 11.3 mol % (13.5 wt %) of structural units derived from divinylbenzene, 5.79 mol % (7.04 wt %) of structural units derived from ethylvinylbenzene, and 82.9 mol % (79.4 wt %) of structural units derived from styrene. The crosslinked structural unit (a2) was 5.86 mol % (7.02 wt %) with a crosslinking degree of 0.52, and the vinyl group-containing structural unit (a1) was 5.41 mol % (6.48 wt %) with a molar fraction of the vinyl group-containing structural unit (a1) being 0.054. The cured product had a Tg of 162°C, a softening temperature of 280°C or higher, and a weight loss of 1.86 wt% at 350°C. The haze value of the polyfunctional vinyl aromatic copolymer C2B was 0.14.

[0215] Comparative example 3B 2.25 mol (292.9 g) of divinylbenzene, 1.32 mol (172.0 g) of ethylvinylbenzene, 11.4 mol (1190.3 g) of styrene, and 15.0 mol (1532.0 g) of n-propyl acetate were charged into a 5.0 L reactor, and 600 mmol of boron trifluoride diethyl ether complex was added at 70 ° C. and reacted for 4 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, and the copolymer was recovered by degassing under reduced pressure at 60 ° C. The obtained copolymer was weighed, and it was confirmed that 860.8 g of copolymer C3B was obtained.

[0216] Copolymer C3B had an Mn of 2060, an Mw of 30700, and an Mw / Mn of 14.9. Copolymer H contained 20.92 mol% (24.29 wt%) of structural units derived from divinylbenzene, 9.06 mol% (10.68 wt%) of structural units derived from ethylvinylbenzene, and 70.02 mol% (65.03 wt%) of structural units derived from styrene. The crosslinked structural unit (a2) was 11.30 mol % (13.12 wt %) with a crosslinking degree of 0.54, and the vinyl group-containing structural unit (a1) was 9.62 mol % (11.17 wt %) with a molar fraction of the vinyl group-containing structural unit (a1) being 0.096. The cured product had no Tg, a softening temperature of 280°C or higher, and a weight loss of 2.11 wt% at 350°C. The haze value of the polyfunctional vinyl aromatic copolymer C3B was 0.17.

[0217] Comparative example 4B 3.1 mol (404.5g) of divinylbenzene, 1.8 mol (237.6g) of ethylvinylbenzene, 7.5 mol (780.7g) of styrene, and 13.0 mol (1325.7g) of n-propyl acetate were charged into a 5.0L reactor, and 193 mmol of boron trifluoride diethyl ether complex was added at 70°C and reacted for 4 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, and the copolymer was recovered by degassing under reduced pressure at 60°C. The obtained copolymer was weighed, and it was confirmed that 689.2g of copolymer C4B was obtained.

[0218] The copolymer C4B had an Mn of 2940, an Mw of 39500, and an Mw / Mn of 13.4. The copolymer C4B contained 36.8 mol % (40.7 wt %) of structural units derived from divinylbenzene, 14.5 mol % (16.3 wt %) of structural units derived from ethylvinylbenzene, and 48.6 mol % (43.0 wt %) of structural units derived from styrene. The crosslinked structural unit (a2) was 20.99 mol % (23.20 wt %) with a crosslinking degree of 0.57, and the vinyl group-containing structural unit (a1) was 15.84 mol % (17.50 wt %) with a molar fraction of the vinyl group-containing structural unit (a1) of 0.158. The cured product had no Tg, a softening temperature of 280°C or higher, and a weight loss at 350°C of 2.23 wt%. The haze value of the polyfunctional vinyl aromatic copolymer C4B was 0.21.

[0219] Example 6B Into a nitrogen-purged autoclave reactor having an internal volume of 0.5 liters, 245 g of cyclohexane, 2.5 g of THF, 10 g of styrene, 40 g of 1,3-butadiene, and 0.50 g of the polyfunctional vinyl aromatic copolymer 1B obtained in Example 1B were added. At 25°C, 5 g of a cyclohexane solution containing 50 mg of sec-butyllithium was added to initiate polymerization. The temperature of the reaction solution increased due to the heat of polymerization, and the maximum temperature reached 85°C. After confirming that the polymerization conversion rate reached 99%, 50 mg of isopropanol was added to terminate the polymerization, and 2,6-di-tert-butyl-p-cresol (BHT) was added to the reaction solution. Then, the solvent was removed by steam stripping to obtain conjugated diene copolymer 6B. The physical properties of the obtained conjugated diene copolymer 6B are shown in Table 1B.

[0220] Example 7B 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.50g of the polyfunctional vinyl aromatic copolymer 1B obtained in Example 1B was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane and no gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 85°C. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Then, the solvent was removed by steam stripping to obtain conjugated diene copolymer 7B. The physical properties of the obtained conjugated diene copolymer 7B are shown in Table 1B.

[0221] Example 8B 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.30g of the polyfunctional vinyl aromatic copolymer 2B obtained in Example 2B was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane and no gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 85°C. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Then, the solvent was removed by steam stripping to obtain conjugated diene copolymer 8B. The physical properties of the obtained conjugated diene copolymer 8B are shown in Table 1B.

[0222] Example 9B 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.50g of the polyfunctional vinyl aromatic copolymer 1B obtained in Example 1B was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane, and no gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the polymerization heat, and the maximum temperature reached 81°C. After the polymerization reaction was completed, 21mmol of BTESPA was added as a modifier to the reactor to carry out a modification reaction. The modification reaction was carried out for 5 minutes at a temperature condition of 80°C to obtain a polymer solution. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Then, the solvent was removed by steam stripping to obtain conjugated diene copolymer 9B. The physical properties of the obtained conjugated diene copolymer 9B are shown in Table 1B.

[0223] Example 10B 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.35g of the polyfunctional vinyl aromatic copolymer 2B obtained in Example 2B was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane, and no gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the polymerization heat, and the maximum temperature reached 81°C. After the polymerization reaction was completed, 21mmol of BTESPA was added as a modifier to the reactor to carry out a modification reaction. The modification reaction was carried out for 5 minutes at a temperature condition of 80°C to obtain a polymer solution. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Then, the solvent was removed by steam stripping to obtain a conjugated diene copolymer 10B. The physical properties of the obtained conjugated diene copolymer 10B are shown in Table 1B.

[0224] Example 11B 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.030g of the polyfunctional vinyl aromatic copolymer 3B obtained in Example 3B was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was mostly soluble in cyclohexane, but gel generation was observed visually. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 82°C. After the polymerization reaction was completed, 21 mmol of BTESPA was added to the reactor as a modifier to carry out the modification reaction. The modification reaction was carried out for 5 minutes at a temperature condition of 80°C to obtain a polymer solution. After it was confirmed that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Next, the solvent was removed by steam stripping to obtain a conjugated diene copolymer 11B. The physical properties of the obtained conjugated diene copolymer 11B are shown in Table 1B.

[0225] Example 12B 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.25g of the polyfunctional vinyl aromatic copolymer 4B obtained in Example 4B was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane, and no gel formation was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 81°C. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Then, the solvent was removed by steam stripping to obtain conjugated diene copolymer 12B. The physical properties of the obtained conjugated diene copolymer 12B are shown in Table 1B.

[0226] Example 13B 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.15g of the polyfunctional vinyl aromatic copolymer 5B obtained in Example 5B was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was partially soluble in cyclohexane, and the generation of gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 81°C. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Then, the solvent was removed by steam stripping to obtain conjugated diene copolymer 13B. The physical properties of the obtained conjugated diene copolymer 13B are shown in Table 1B.

[0227] Comparative Example 5B 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.5g of the polyfunctional vinyl aromatic copolymer C1B obtained in Comparative Example 1B was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was partially soluble in cyclohexane, and the generation of gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 84°C. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. The solvent was then removed by steam stripping to obtain a conjugated diene copolymer C5B. The physical properties of the obtained conjugated diene copolymer C5B are shown in Table 1B.

[0228] Comparative Example 6B 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.030g of the polyfunctional vinyl aromatic copolymer C2B obtained in Comparative Example 2B was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was mostly soluble in cyclohexane, but the generation of gel was observed visually. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the polymerization heat, and the maximum temperature reached 83°C. After the polymerization reaction was completed, 21mmol of BTESPA was added as a modifier to the reactor to carry out a modification reaction. The modification reaction was carried out for 5 minutes at a temperature condition of 80°C to obtain a polymer solution. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. The solvent was then removed by steam stripping to obtain a conjugated diene copolymer C6B. The physical properties of the obtained conjugated diene copolymer C6B are shown in Table 1B.

[0229] Comparative example 7B 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.25g of the polyfunctional vinyl aromatic copolymer C3B obtained in Comparative Example 3B was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane, and no gel formation was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 83°C. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Then, the solvent was removed by steam stripping to obtain a conjugated diene copolymer C7B. The physical properties of the obtained conjugated diene copolymer C7B are shown in Table 1B.

[0230] Comparative Example 8B 200g of cyclohexane and 2.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 50mg (0.78mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.15g of the polyfunctional vinyl aromatic copolymer C4B obtained in Comparative Example 4B was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was partially soluble in cyclohexane, and the generation of gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 83°C. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. The solvent was then removed by steam stripping to obtain a conjugated diene copolymer C8B. The physical properties of the obtained conjugated diene copolymer C8B are shown in Table 1B.

[0231] [Table 1B]

[0232] Example 14B Conjugated diene copolymer 6B, process oil, carbon black, zinc oxide, stearic acid and an antioxidant were kneaded at 155° C. and 60 rpm for 4 minutes using a Labo Plastomill. To the kneaded product obtained by the above kneading, sulfur and a vulcanization accelerator were added, and the mixture was kneaded at 70° C. and 60 rpm for 1 minute using a Labo Plastomill, and vulcanized to obtain a crosslinked rubber 14B. The additives and their mixing ratios are the same as those in Table 2A. The physical properties of the crosslinked rubber 14B are shown in Table 3B.

[0233] Examples 15B to 21B, Comparative Examples 9B to 12B Crosslinked rubbers 14B to 21B and C9B to C12B were obtained in the same manner as in Example 14B, except that the conjugated diene copolymers 7B to 13B and C5B to C8B synthesized in the above examples or comparative examples were used instead of the conjugated diene copolymer 6B. The types of conjugated diene copolymers used and the physical properties of the resulting crosslinked rubbers 14B to 21B and C9B to C12B are shown in Table 3B.

[0234] [Table 3B]

[0235] From Table 3B, it can be seen that the cross-linked rubber of the present invention using the polyfunctional vinyl aromatic copolymer of the present invention has equal or better processability than the case using divinylbenzene, a known branching agent, and is excellent in tensile strength and abrasion resistance in vulcanized rubber blended with carbon black.

[0236] <Third embodiment of the present invention> Example 1C 31.00g of DVB-630 (divinylbenzene component 0.150 mol, ethylvinylbenzene (mixture of m- and p-forms) component 0.088 mol), 65.72g (0.631 mol) of styrene, 70.80g (0.631 mol) of diisobutylene, 60 mmol (6.90mL) of n-propyl acetate, and 48.55g (0.527 mol) of toluene were charged into a 500mL reactor, and 15.2 mmol of boron trifluoride diethyl ether complex (1.91mL) was added at 70°C and reacted for 2.0 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, and the copolymer was removed under reduced pressure at 60°C, and 60.6g of polyfunctional vinyl aromatic copolymer 1C was obtained.

[0237] The resulting polyfunctional vinyl aromatic copolymer 1C had an Mn of 941, an Mw of 2850, and an Mw / Mn of 3.03. 13 C-NMR and 1 By H-NMR analysis, the polyfunctional vinyl aromatic copolymer A contained 19.0 mol% (21.8 wt%) of structural units derived from divinylbenzene, 8.3 mol% (9.6 wt%) of structural units derived from ethylvinylbenzene, 48.6 mol% (44.6 wt%) of structural units derived from styrene, and 24.2 mol% (24.0 wt%) of structural units derived from diisobutylene. The crosslinked structural units (a2) derived from the divinyl aromatic compound represented by the formula (2) were 4.6 mol% (5.2 wt%), so the crosslinking degree (a2 / a) was 0.24. In addition, the structural units (a1) derived from divinylbenzene having residual vinyl groups contained in the polyfunctional vinyl aromatic copolymer 1C were 14.4 mol% (16.5 wt%), so the molar fraction of the vinyl group-containing structural units (a1) relative to the sum of the structural units (a), (b), and (c) was 0.144. Furthermore, TMA measurement of the cured product showed that the Tg was 167°C and the softening temperature was 280°C or higher. The TGA measurement results showed that the weight loss at 350°C was 1.41wt%. A sample prepared by dissolving 0.5g of polyfunctional vinyl aromatic copolymer 1C in 100g of toluene was placed in a quartz cell, and the haze (turbidity) was measured using an integrating sphere light transmittance measuring device with toluene as the reference sample. The haze value was 0.02.

[0238] Example 2C DVB-630 46.49g (divinylbenzene component 0.225 mol, ethylvinylbenzene component 0.132 mol), styrene 53.33g (0.512 mol), diisobutylene 70.80g (0.631 mol), n-propyl acetate 60 mmol (6.90mL), toluene 48.55g (0.527 mol) were charged into a 500mL reactor, and 10.0 mmol of boron trifluoride diethyl ether complex (1.26mL) was added at 70°C and reacted for 2.0 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, and the copolymer was removed under reduced pressure at 60°C, and 66.4g of polyfunctional vinyl aromatic copolymer 2C was obtained.

[0239] The resulting polyfunctional vinyl aromatic copolymer 2C had an Mn of 1240, an Mw of 4980, and an Mw / Mn of 4.02. 13 C-NMR and 1 By carrying out H-NMR analysis, the polyfunctional vinyl aromatic copolymer B contained 28.2 mol% (31.5 wt%) of structural units derived from divinylbenzene, 12.2 mol% (13.8 wt%) of structural units derived from ethylvinylbenzene, 37.6 mol% (33.6 wt%) of structural units derived from styrene, and 22.0 mol% (21.1 wt%) of structural units derived from diisobutylene. The crosslinked structural units (a2) derived from the divinyl aromatic compound represented by the formula (2) were 7.6 mol% (8.5 wt%), so the degree of crosslinking was 0.27. In addition, the structural units (a1) derived from divinylbenzene having residual vinyl groups contained in the polyfunctional vinyl aromatic copolymer 2C were 20.6 mol% (23.0 wt%), so the molar fraction of the vinyl group-containing structural units (a1) relative to the sum of the structural units (a), (b), and (c) was 0.206. Furthermore, TMA measurement of the cured product showed that it had a Tg of 176°C and a softening temperature of 280°C or higher. The TGA measurement results showed that the weight loss at 350°C was 1.32wt%. A sample prepared by dissolving 0.5g of polyfunctional vinyl aromatic copolymer 2C in 100g of toluene was placed in a quartz cell, and the haze (turbidity) was measured using an integrating sphere light transmittance measuring device with toluene as the reference sample. The haze value was 0.03.

[0240] Example 3C 62.00g of DVB-630 (divinylbenzene component 0.300 mol, ethylvinylbenzene component 0.176 mol), 40.92g (0.393 mol) of styrene, 70.80g (0.631 mol) of diisobutylene, 60 mmol (6.90mL) of n-propyl acetate, and 48.55g (0.527 mol) of toluene were charged into a 500mL reactor, and 8.2 mmol of boron trifluoride diethyl ether complex (1.03mL) was added at 70°C and reacted for 1.5 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, and the copolymer was removed under reduced pressure at 60°C, and 56.3g of polyfunctional vinyl aromatic copolymer 3C was obtained.

[0241] The resulting polyfunctional vinyl aromatic copolymer 3C had an Mn of 1430, an Mw of 5490, and an Mw / Mn of 3.84. 13 C-NMR and 1By carrying out H-NMR analysis, the polyfunctional vinyl aromatic copolymer C contained 39.4 mol% (42.6 wt%) of structural units derived from divinylbenzene, 15.9 mol% (17.4 wt%) of structural units derived from ethylvinylbenzene, 25.7 mol% (22.2 wt%) of structural units derived from styrene, and 19.1 mol% (17.8 wt%) of structural units derived from diisobutylene. The crosslinked structural units (a2) derived from the divinyl aromatic compound represented by the formula (2) were 11.4 mol% (12.3 wt%), so the degree of crosslinking was 0.29. In addition, the structural units (a1) derived from divinylbenzene having residual vinyl groups contained in the polyfunctional vinyl aromatic copolymer 3C were 28.0 mol% (30.2 wt%), so the molar fraction of the vinyl group-containing structural units (a1) relative to the sum of the structural units (a), (b), and (c) was 0.280. Furthermore, TMA measurement of the cured product showed that the Tg was 183°C and the softening temperature was 280°C or higher. The TGA measurement results showed that the weight loss at 350°C was 1.28wt%. A sample prepared by dissolving 0.5g of polyfunctional vinyl aromatic copolymer 3C in 100g of toluene was placed in a quartz cell, and the haze (turbidity) was measured using an integrating sphere light transmittance measuring device with toluene as the reference sample. The haze value was 0.05.

[0242] Comparative example 1C 320.5mL of DVB-810 (1.82 mol of divinylbenzene component, 0.43 mol of ethylvinylbenzene component), 0.28 mol (36.9mL) of n-butyl acetate, and 140mL of toluene were charged into a 1.0L reactor, and a solution of 40 mmol of methanesulfonic acid dissolved in 0.12 mol (15.7mL) of n-butyl acetate was added at 70°C, and the reaction was carried out for 6 hours. After the polymerization solution was stopped with calcium hydroxide, filtration was carried out using activated alumina as a filter aid. Then, the mixture was devolatilized under reduced pressure at 60°C to obtain 22.6g of polyfunctional vinyl aromatic copolymer C1C. The polyfunctional vinyl aromatic copolymer C1C had an Mn of 1085, an Mw of 12400, and an Mw / Mn of 11.4, and contained 84.0 mol % (83.8 wt %) of structural units derived from divinylbenzene and a total of 16.0 mol % (16.2 wt %) of structural units derived from ethylvinylbenzene. The crosslinked structural units (a2) were 2.60 mol % (2.59 wt %), the degree of crosslinking was 0.031, the vinyl group-containing structural units (a1) were 11.40 mol % (11.37 wt %), and the molar fraction of the vinyl group-containing structural units (a1) was 0.114. The cured product had a Tg of 82° C., a softening temperature of 93° C., and a weight loss of 8.25 wt% at 350° C. On the other hand, compatibility with epoxy resins was rated as good. The haze value of the polyfunctional vinyl aromatic copolymer C1C was 0.02.

[0243] Comparative Example 2C 1.5 mol (195.3 g) of divinylbenzene, 0.88 mol (114.7 g) of ethylvinylbenzene, 12.6 mol (1314.3 g) of styrene, and 15.0 mol (1532.0 g) of n-propyl acetate were charged into a 5.0 L reactor, and 600 mmol of boron trifluoride diethyl ether complex was added at 70 ° C. and reacted for 4 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, and the copolymer was recovered by degassing under reduced pressure at 60 ° C. The obtained copolymer was weighed, and it was confirmed that 820.8 g of copolymer C2C was obtained.

[0244] The copolymer C2C had an Mn of 1490, an Mw of 12600, and an Mw / Mn of 8.44. The copolymer C2C contained 11.3 mol% (13.5 wt%) of structural units derived from divinylbenzene, 5.79 mol% (7.04 wt%) of structural units derived from ethylvinylbenzene, and 82.9 mol% (79.4 wt%) of structural units derived from styrene. The crosslinked structural unit (a2) was 5.86 mol % (7.02 wt %) with a crosslinking degree of 0.52, and the vinyl group-containing structural unit (a1) was 5.41 mol % (6.48 wt %) with a molar fraction of the vinyl group-containing structural unit (a1) being 0.054. The cured product had a Tg of 162°C, a softening temperature of 280°C or higher, and a weight loss of 1.86 wt% at 350°C. The haze value of the polyfunctional vinyl aromatic copolymer C2C was 0.14.

[0245] Comparative example 3C 2.25 mol (292.9 g) of divinylbenzene, 1.32 mol (172.0 g) of ethylvinylbenzene, 11.4 mol (1190.3 g) of styrene, and 15.0 mol (1532.0 g) of n-propyl acetate were charged into a 5.0 L reactor, and 600 mmol of boron trifluoride diethyl ether complex was added at 70 ° C. and reacted for 4 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, and the copolymer was recovered by degassing under reduced pressure at 60 ° C. The copolymer obtained was weighed, and it was confirmed that 860.8 g of copolymer C3C was obtained.

[0246] The copolymer C3C had an Mn of 2060, an Mw of 30700, and an Mw / Mn of 14.9. The copolymer C3C contained 20.92 mol% (24.29 wt%) of structural units derived from divinylbenzene, 9.06 mol% (10.68 wt%) of structural units derived from ethylvinylbenzene, and 70.02 mol% (65.03 wt%) of structural units derived from styrene. The crosslinked structural unit (a2) was 11.30 mol % (13.12 wt %) with a crosslinking degree of 0.54, and the vinyl group-containing structural unit (a1) was 9.62 mol % (11.17 wt %) with a molar fraction of the vinyl group-containing structural unit (a1) being 0.096. The cured product had no Tg, a softening temperature of 280°C or higher, and a weight loss of 2.11 wt% at 350°C. The haze value of the polyfunctional vinyl aromatic copolymer C3C was 0.17.

[0247] Comparative Example 4C 3.1 mol (404.5g) of divinylbenzene, 1.8 mol (237.6g) of ethylvinylbenzene, 7.5 mol (780.7g) of styrene, and 13.0 mol (1325.7g) of n-propyl acetate were charged into a 5.0L reactor, and 193 mmol of boron trifluoride diethyl ether complex was added at 70°C and reacted for 4 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, and the copolymer was recovered by degassing under reduced pressure at 60°C. The obtained copolymer was weighed, and it was confirmed that 689.2g of copolymer C4C was obtained.

[0248] The copolymer C4C had an Mn of 2940, an Mw of 39500, and an Mw / Mn of 13.4. The copolymer C4C contained 36.8 mol % (40.7 wt %) of structural units derived from divinylbenzene, 14.5 mol % (16.3 wt %) of structural units derived from ethylvinylbenzene, and 48.6 mol % (43.0 wt %) of structural units derived from styrene. The crosslinked structural unit (a2) was 20.99 mol % (23.20 wt %) with a crosslinking degree of 0.57, and the vinyl group-containing structural unit (a1) was 15.84 mol % (17.50 wt %) with a molar fraction of the vinyl group-containing structural unit (a1) of 0.158. The cured product had no Tg, a softening temperature of 280°C or higher, and a weight loss at 350°C of 2.23 wt%. The haze value of the functional vinyl aromatic copolymer C4C was 0.21.

[0249] Example 4C Into a nitrogen-purged autoclave reactor having an internal volume of 0.5 liters, 245 g of cyclohexane, 0.5 g of THF, 10 g of styrene, 40 g of 1,3-butadiene, and 0.10 g of the polyfunctional vinyl aromatic copolymer 1C obtained in Example 1C were added. At 25°C, 5 g of a cyclohexane solution containing 10 mg (0.16 mmol) of sec-butyl lithium was added to initiate polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and reached a maximum temperature of 81°C. After confirming that the polymerization conversion rate reached 99%, 50 mg of isopropanol was added to terminate the polymerization, and 2,6-di-tert-butyl-p-cresol (BHT) was added to the reaction solution. Next, the solvent was removed by steam stripping to obtain a conjugated diene copolymer 4C. 0.5 g of the obtained conjugated diene copolymer 4C was dissolved in 100 mL of toluene, and colored by adding 1.0 g of a 0.2 wt% Sudan III toluene solution, and filtered with a 0.2 μm PTFE membrane filter. When the membrane filter after filtration was observed with a microscope, it was confirmed that no microgel was generated. The physical properties of the conjugated diene copolymer 4C are shown in Table 1C.

[0250] Example 5C 200g of cyclohexane and 0.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 10mg (0.16mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.10g of the polyfunctional vinyl aromatic copolymer 1C obtained in Example 1C was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane and no gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 80°C. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Next, the solvent was removed by steam stripping to obtain a conjugated diene copolymer 5C. 0.5 g of the obtained conjugated diene copolymer 5C was dissolved in 100 mL of toluene, and 1.0 g of a 0.2 wt% Sudan III toluene solution was added to color the mixture. The mixture was filtered through a 0.2 μm PTFE membrane filter, and the membrane filter after filtration was observed under a microscope, confirming that no microgel was formed. The physical properties of the conjugated diene copolymer 5C are shown in Table 1C.

[0251] Example 6C 200g of cyclohexane and 0.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 10mg (0.16mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.085g of the polyfunctional vinyl aromatic copolymer 2C obtained in Example 2C was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane and no gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 83°C. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Next, the solvent was removed by steam stripping to obtain a conjugated diene copolymer 6C. 0.5 g of the obtained conjugated diene copolymer 6C was dissolved in 100 mL of toluene, and 1.0 g of a 0.2 wt% Sudan III toluene solution was added to color the mixture. The mixture was filtered through a 0.2 μm PTFE membrane filter, and the membrane filter after filtration was observed under a microscope, confirming that no microgel was formed. The physical properties of the conjugated diene copolymer 6C are shown in Table 1C.

[0252] Example 7C In a nitrogen-substituted autoclave reactor, 200 g of cyclohexane and 0.5 g of THF were charged, and 5 g of a cyclohexane solution containing 10 mg (0.16 mmol) of n-butyl lithium as a pure content was added at 50° C., and then 45 g of a cyclohexane solution containing 0.10 g of the polyfunctional vinyl aromatic copolymer 1C obtained in Example 1C was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane, and no gel was observed. 10 g of styrene and 40 g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the polymerization heat, and the maximum temperature reached 81° C. After the polymerization reaction was completed, 21 mmol of BTESPA was added as a modifier to the reactor to carry out a modification reaction. The modification reaction was carried out for 5 minutes at a temperature condition of 80° C. to obtain a polymer solution. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Next, the solvent was removed by steam stripping to obtain a conjugated diene copolymer 7C. 0.5 g of the obtained conjugated diene copolymer 7C was dissolved in 100 mL of toluene, and 1.0 g of a 0.2 wt% Sudan III toluene solution was added to color the mixture. The mixture was filtered through a 0.2 μm PTFE membrane filter, and the membrane filter after filtration was observed under a microscope, confirming that no microgel was formed. The physical properties of the conjugated diene copolymer 7C are shown in Table 1C.

[0253] Example 8C 200g of cyclohexane and 0.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 10mg (0.16mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.085g of the polyfunctional vinyl aromatic copolymer 2C obtained in Example 2C was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane, and no gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the polymerization heat, and the maximum temperature reached 82°C. After the polymerization reaction was completed, 21mmol of BTESPA was added as a modifier to the reactor to carry out a modification reaction. The modification reaction was carried out for 5 minutes at a temperature condition of 80°C to obtain a polymer solution. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Next, the solvent was removed by steam stripping to obtain a conjugated diene copolymer 8C. 0.5 g of the obtained conjugated diene copolymer 8C was dissolved in 100 mL of toluene, and colored by adding 1.0 g of a 0.2 wt% Sudan III toluene solution, and filtered with a 0.2 μm PTFE membrane filter. When the membrane filter after filtration was observed with a microscope, it was confirmed that no microgel was generated. The physical properties of the conjugated diene copolymer 8C are shown in Table 1C.

[0254] Example 9C 200g of cyclohexane and 0.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 10mg (0.16mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.070g of the polyfunctional vinyl aromatic copolymer 3C obtained in Example 3C was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane, and no gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the polymerization heat, and the maximum temperature reached 78°C. After the polymerization reaction was completed, 21mmol of BTESPA was added as a modifier to the reactor to carry out a modification reaction. The modification reaction was carried out for 5 minutes at a temperature condition of 80°C to obtain a polymer solution. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Next, the solvent was removed by steam stripping to obtain a conjugated diene copolymer 9C. 0.5 g of the obtained conjugated diene copolymer 9C was dissolved in 100 mL of toluene, and colored by adding 1.0 g of a 0.2 wt% Sudan III toluene solution, and filtered with a 0.2 μm PTFE membrane filter. When the membrane filter after filtration was observed with a microscope, it was confirmed that no microgel was generated. The physical properties of the conjugated diene copolymer 9C are shown in Table 1C.

[0255] Comparative Example 5C 200g of cyclohexane and 0.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 10mg (0.16mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.1g of the polyfunctional vinyl aromatic copolymer C1C obtained in Comparative Example 1C was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was partially soluble in cyclohexane, but the generation of gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 84°C. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Next, the solvent was removed by steam stripping to obtain a conjugated diene copolymer C5C. 0.5 g of the obtained conjugated diene copolymer C5C was dissolved in 100 mL of toluene, and colored by adding 1.0 g of a 0.2 wt% Sudan III toluene solution, and filtered with a 0.2 μm PTFE membrane filter. The membrane filter after filtration was observed with a microscope, and the formation of a microgel was confirmed. The physical properties of the conjugated diene copolymer C5C are shown in Table 1C.

[0256] Comparative Example 6C 200g of cyclohexane and 0.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 10mg (0.16mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.08g of the polyfunctional vinyl aromatic copolymer C2C obtained in Comparative Example 2C was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was mostly soluble in cyclohexane, but the generation of gel was observed visually. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the polymerization heat, and the maximum temperature reached 83°C. After the polymerization reaction was completed, 21mmol of BTESPA was added as a modifier to the reactor to carry out a modification reaction. The modification reaction was carried out for 5 minutes at a temperature condition of 80°C to obtain a polymer solution. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Next, the solvent was removed by steam stripping to obtain a conjugated diene copolymer C6C. 0.5 g of the obtained conjugated diene copolymer C6C was dissolved in 100 mL of toluene, and colored by adding 1.0 g of a 0.2 wt% Sudan III toluene solution, and filtered through a 0.2 μm PTFE membrane filter. The membrane filter after filtration was observed with a microscope, and the formation of a microgel was confirmed. The physical properties of the conjugated diene copolymer C6C are shown in Table 1C.

[0257] Comparative example 7C In a nitrogen-substituted autoclave reactor, 200 g of cyclohexane and 0.5 g of THF were charged, and 5 g of a cyclohexane solution containing 10 mg (0.16 mmol) of n-butyl lithium as a pure content was added at 50°C. Then, 45 g of a cyclohexane solution containing 0.10 g of the polyfunctional vinyl aromatic copolymer C3C obtained in Comparative Example 3C was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane, but the generation of gel was observed. 10 g of styrene and 40 g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 83°C. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Next, the solvent was removed by steam stripping to obtain a conjugated diene copolymer C7C. 0.5 g of the obtained conjugated diene copolymer C7C was dissolved in 100 mL of toluene, and colored by adding 1.0 g of a 0.2 wt% Sudan III toluene solution, and filtered with a 0.2 μm PTFE membrane filter. The membrane filter after filtration was observed with a microscope, and the formation of a microgel was confirmed. The physical properties of the conjugated diene copolymer C7C are shown in Table 1C.

[0258] Comparative Example 8C 200g of cyclohexane and 0.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 10mg (0.16mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.08g of the polyfunctional vinyl aromatic copolymer C4C obtained in Comparative Example 4C was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was partially soluble in cyclohexane, but the generation of gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the heat of polymerization, and the maximum temperature reached 83°C. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Next, the solvent was removed by steam stripping to obtain a conjugated diene copolymer C8C. 0.5 g of the obtained conjugated diene copolymer C8C was dissolved in 100 mL of toluene, and colored by adding 1.0 g of a 0.2 wt% Sudan III toluene solution, and filtered with a 0.2 μm PTFE membrane filter. The membrane filter after filtration was observed with a microscope, and the formation of a microgel was confirmed. The physical properties of the conjugated diene copolymer C8C are shown in Table 1C.

[0259] [Table 1C]

[0260] Example 10C The conjugated diene copolymer 4C (copolymer rubber) synthesized in Example 4C, process oil, carbon black, zinc oxide, stearic acid and an antioxidant were blended and kneaded at 155° C. and 60 rpm for 4 minutes using a Labo Plastomill. To the kneaded product obtained by the above kneading, sulfur and a vulcanization accelerator were added, and the mixture was kneaded at 70° C. and 60 rpm for 1 minute using a Labo Plastomill, and vulcanized to obtain a crosslinked rubber 10C. The mixing ratio of each additive is shown in Table 2C, and the physical properties of crosslinked rubber 10C are shown in Table 3C.

[0261] [Table 2C]

[0262] The additives used are as follows: Process oil: Idemitsu Kosan Dyna Process Oil AC-12 Silica: Degussa, ULTRASIL VN3 Carbon black: Nitelon #300 made by Nippon Steel Carbon Zinc oxide: Zinc oxide No. 1 manufactured by Mitsui Mining & Smelting Stearic acid: NOF Corporation Anti-aging agent: Noccela NS manufactured by Ouchi Shinko Chemical Industry Sulfur: Powdered sulfur manufactured by Tsurumi Chemical Industry Co., Ltd. Accelerator: N-tert-butylbenzothiazole-2-sulfenamide

[0263] Examples 11C to 15C, Comparative Examples 9C to 12C Crosslinked rubbers 11C to 15C and C9C to C12C were obtained in the same manner as in Example 10C, except that the conjugated diene copolymers 5C to 9C and C5C to C8C synthesized in the above Examples or Comparative Examples were used instead of the conjugated diene copolymer 4C. The types of conjugated diene copolymers used and the physical properties of the resulting crosslinked rubbers 11C to 15C and C9C to C12C are shown in Table 3C.

[0264] [Table 3C]

[0265] From Table 3C, it can be seen that the cross-linked rubber of the present invention using the polyfunctional vinyl aromatic copolymer of the present invention gives equal or greater silica dispersibility and adhesion at the interface compared to the case using divinylbenzene, a known branching agent, and therefore has excellent tensile strength and abrasion resistance in the vulcanized rubber.

[0266] Example 16C DVB-630 46.49g (divinylbenzene component 0.225 mol, ethylvinylbenzene component 0.132 mol), styrene 53.33g (0.512 mol), 2-methyl-1-hexene 61.95g (0.631 mol), n-propyl acetate 60 mmol (6.90mL), toluene 48.55g (0.527 mol) were charged into a 500mL reactor, and 10.0 mmol of boron trifluoride diethyl ether complex (1.26mL) was added at 70°C and reacted for 2.0 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, and the copolymer was removed under reduced pressure at 60°C, and 64.8g of polyfunctional vinyl aromatic copolymer 16C was obtained.

[0267] The resulting polyfunctional vinyl aromatic copolymer 16C had an Mn of 1310, an Mw of 5070, and an Mw / Mn of 3.87. 13 C-NMR and 1 H-NMR analysis revealed that the polyfunctional vinyl aromatic copolymer J contained 28.0 mol % (32.2 wt %) of structural units derived from divinylbenzene, 12.2 mol % (14.2 wt %) of structural units derived from ethylvinylbenzene, 32.5 mol % (35.3 wt %) of structural units derived from styrene, and 24.5 mol % (21.2 wt %) of structural units derived from 2-methyl-1-hexene. The crosslinked structural unit (a2) derived from the divinyl aromatic compound represented by the formula (2) was 8.1 mol % (9.3 wt %), so the degree of crosslinking was 0.29. The structural unit (a1) derived from divinylbenzene having a residual vinyl group contained in the polyfunctional vinyl aromatic copolymer J was 19.9 mol % (22.8 wt %), so the molar fraction of the vinyl group-containing structural unit (a1) relative to the total of the structural units (a), (b), and (c) was 0.199. Furthermore, TMA measurement of the cured product showed that Tg was 168°C and the softening temperature was 280°C or higher. The TGA measurement results showed that the weight loss at 350°C was 1.41wt%. A sample prepared by dissolving 0.5g of polyfunctional vinyl aromatic copolymer 16C in 100g of toluene was placed in a quartz cell, and the haze (turbidity) was measured using an integrating sphere light transmittance measuring device with toluene as the reference sample. The haze value was 0.04.

[0268] Example 17C DVB-630 46.49g (divinylbenzene component 0.225 mol, ethylvinylbenzene component 0.132 mol), styrene 53.33g (0.512 mol), 2-methyl-1-pentene 53.10g (0.631 mol), n-propyl acetate 60 mmol (6.90mL), toluene 48.55g (0.527 mol) were charged into a 500mL reactor, and 10.0 mmol of boron trifluoride diethyl ether complex (1.26mL) was added at 70°C and reacted for 2.0 hours. After the polymerization solution was stopped with an aqueous sodium hydrogen carbonate solution, the oil layer was washed three times with pure water, and the copolymer was removed under reduced pressure at 60°C, and 61.5g of polyfunctional vinyl aromatic copolymer 17C was obtained.

[0269] The resulting polyfunctional vinyl aromatic copolymer 17C had an Mn of 1280, an Mw of 5260, and an Mw / Mn of 4.11. 13 C-NMR and 1 H-NMR analysis revealed that the polyfunctional vinyl aromatic copolymer 17C contained 26.5 mol % (31.7 wt %) of structural units derived from divinylbenzene, 11.3 mol % (13.8 wt %) of structural units derived from ethylvinylbenzene, 35.3 mol % (33.8 wt %) of structural units derived from styrene, and 26.8 mol % (20.8 wt %) of structural units derived from 2-methyl-1-pentene. The crosslinked structural unit (a2) derived from the divinyl aromatic compound represented by the formula (2) was 7.2 mol % (8.6 wt %), so the degree of crosslinking was 0.27. The structural unit (a1) derived from divinylbenzene having a residual vinyl group contained in the polyfunctional vinyl aromatic copolymer B was 19.3 mol % (23.1 wt %), so the molar fraction of the vinyl group-containing structural unit (a1) relative to the total of the structural units (a), (b), and (c) was 0.193. Furthermore, TMA measurement of the cured product showed that Tg was 171°C and the softening temperature was 280°C or higher. The TGA measurement results showed that the weight loss at 350°C was 1.38wt%. A sample prepared by dissolving 0.5g of polyfunctional vinyl aromatic copolymer 17C in 100g of toluene was placed in a quartz cell, and the haze (turbidity) was measured using an integrating sphere light transmittance measuring device with toluene as the reference sample. The haze value was 0.03.

[0270] Example 18C Into a nitrogen-substituted autoclave reactor, 200 g of cyclohexane and 0.5 g of THF were charged, and at 50° C., 5 g of a cyclohexane solution containing 10 mg (0.16 mmol) of n-butyl lithium as a pure content was added, and then 45 g of a cyclohexane solution containing 0.085 g of the polyfunctional vinyl aromatic copolymer 16C obtained in Example 16C was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane, and no gel was observed. 10 g of styrene and 40 g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the polymerization heat, and the maximum temperature reached 82° C. After the polymerization reaction was completed, 21 mmol of BTESPA was added as a modifier to the reactor to carry out a modification reaction. The modification reaction was carried out for 5 minutes at a temperature condition of 80° C. to obtain a polymer solution. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Next, the solvent was removed by steam stripping to obtain a conjugated diene copolymer 18C. 0.5 g of the obtained conjugated diene copolymer 18C was dissolved in 100 mL of toluene, and colored by adding 1.0 g of a 0.2 wt% Sudan III toluene solution, and filtered with a 0.2 μm PTFE membrane filter. When the membrane filter after filtration was observed with a microscope, it was confirmed that no microgel was generated. The physical properties of the conjugated diene copolymer 18C are shown in Table 4C.

[0271] Example 19C 200g of cyclohexane and 0.5g of THF were charged into a nitrogen-substituted autoclave reactor, and 5g of a cyclohexane solution containing 10mg (0.16mmol) of n-butyllithium as a pure content was added at 50°C. Then, 45g of a cyclohexane solution containing 0.085g of the polyfunctional vinyl aromatic copolymer 17C obtained in Example 17C was added over 30 minutes to prepare a polyfunctional anionic polymerization initiator. The prepared polyfunctional anionic polymerization initiator was soluble in cyclohexane, and no gel was observed. 10g of styrene and 40g of 1,3-butadiene from which impurities had been removed in advance were added to start polymerization. The temperature of the reaction solution rose due to the polymerization heat, and the maximum temperature reached 82°C. After the polymerization reaction was completed, 21mmol of BTESPA was added as a modifier to the reactor to carry out a modification reaction. The modification reaction was carried out for 5 minutes at a temperature condition of 80°C to obtain a polymer solution. After confirming that the polymerization conversion rate reached 99%, 50 mg (0.83 mmol) of isopropanol was added to terminate the polymerization, and BHT was added to the reaction solution. Next, the solvent was removed by steam stripping to obtain a conjugated diene copolymer 19C. 0.5 g of the obtained conjugated diene copolymer 19C was dissolved in 100 mL of toluene, and colored by adding 1.0 g of a 0.2 wt% Sudan III toluene solution, and filtered with a 0.2 μm PTFE membrane filter. When the membrane filter after filtration was observed with a microscope, it was confirmed that no microgel was generated. The physical properties of the conjugated diene copolymer 19C are shown in Table 4C.

[0272] [Table 4C] [Industrial Applicability]

[0273] The polyfunctional vinyl aromatic copolymer of the present invention can be used as a raw material for conjugated diene copolymer.Furthermore, the crosslinked rubber composition obtained by crosslinking the conjugated diene copolymer containing a filler has excellent filler dispersibility, mechanical strength, and abrasion resistance, and is therefore useful as an elastomer material for tires (especially tire treads), seismic isolation rubber, rubber hoses, rubber rollers, footwear materials, etc. It can also be applied to molding materials, resin modifiers, etc. It can be provided as a dielectric material, insulating material, heat-resistant material, structural material, etc. in the fields of the electrical and electronics industry, the space and aircraft industry, etc. In addition, the film and sheet coated with the curable resin composition containing the polyfunctional vinyl aromatic copolymer of the present invention are suitably used in plastic optical parts, touch panels, flat displays, film liquid crystal elements, etc. The polyfunctional vinyl aromatic copolymer of the present invention can also be used as a modifier for modifying the properties such as heat resistance, dielectric properties, and optical properties of the thermoplastic resin or curable resin composition used as the main material of the film, sheet, and prepreg. In addition, the curable resin composition containing the polyfunctional vinyl aromatic copolymer of the present invention as the main material can be processed into a film, sheet, and prepreg for use. Furthermore, the curable resin composition containing the polyfunctional vinyl aromatic copolymer of the present invention can also be used as various optical elements including optical waveguides and optical lenses.

Claims

1. A polyfunctional vinyl aromatic copolymer containing 5 mol % or more and 30 mol % or less of structural units (a) derived from a divinyl aromatic compound, 5 mol % or more and 20 mol % or less of structural units (b) derived from a monovinyl aromatic compound, and 50 mol % or more and 90 mol % or less of structural units (c) derived from an acenaphthylene-based compound, wherein at least a part of the structural units (a) is a vinyl group-containing structural unit (a1) represented by the following formula (1): 【Chemistry 1】 (In the formula, R1 represents an aromatic hydrocarbon group having 6 to 30 carbon atoms.) A polyfunctional vinyl aromatic copolymer, characterized in that the molar fraction of the vinyl group-containing structural unit (a1) relative to the total of the structural units (a), (b) and (c) is in the range of 0.01 to 0.

30.

2. The polyfunctional vinyl aromatic copolymer according to claim 1, which has a number average molecular weight Mn of 300 to 100,000, a molecular weight distribution (Mw / Mn) represented by the ratio of the weight average molecular weight Mw to the number average molecular weight Mn of 10.0 or less, and is soluble in toluene, xylene, tetrahydrofuran, dichloroethane or chloroform.

3. The method for producing the polyfunctional vinyl aromatic copolymer according to claim 1, characterized in that the polymerization raw materials including the divinyl aromatic compound, the monovinyl aromatic compound and the acenaphthylene-based compound are dissolved in a solvent having a dielectric constant of 2.0 to 15.0, and the polymerization is carried out in a homogeneous solvent in the presence of a Lewis acid catalyst at a temperature of 20 to 120°C.

Citation Information

Patent Citations

  • Soluble polyfunctional vinyl aromatic copolymer, method for producing the same, curable resin composition, and cured product of the same

    JP2018039995A

  • Method for producing block copolymer

    JP2003073434A

  • Soluble, multifunctional vinyl aromatic copolymer and its polymerization process

    JP2004123873A

  • Star-block interpolymers and their manufacture

    JP2004517202A

  • Rubber composition

    JP2005213381A